Suppression of microRNAs targeting key MEP pathway genes affects plastid terpenoid content and photosynthesis under variable light conditions - Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Muhammad Sajad; Muhamad Hafiz Che-Othman; Hoe-Han Goh; Ismanizan Ismail (Molecular Biology Reports, 2026)

Suppression of miR426 enhances photoprotection and chlorophyll stability via upregulation of ELIP2 in Arabidopsis thaliana - Arif Faisal Mustaffa; Syed Muhammad Iqbal Syed Othman; Nur Irdina Izzatie Mohd Zahid; M. Hafiz Che-Othman; Hoe-Han Goh; Muhammad Sajad; Ismanizan Ismail (Molecular Biology Reports, 2026)

Evaluation of the Air Pollution Mitigation Potential of Some Roadside Plants for Urban Forest Management - Mahrukh; Sohaib Muhammad; Muhammad Tayyab; Ali Ahmad; Zaher Uddin Babar; Nahaa M. Alotaibi; Muhammad Bilal; Amr Elkelish; Iqra Parvaz; Bushra Munam; Summiya Faisal; Muhammad Hasnain (Water, Air, & Soil Pollution, 2026)

Genetic dissection and QTL validation of seedling root system architecture in Chinese wheat landraces - Hafiz Muhammad Faisal Umer; Muhammad Junaid Jalil; Huaping Tang; Hang Liu; Md Nahibuzzaman Lohani; Qiang Xu; Zhi Zheng; Yaxi Liu; Jirui Wang; Guoyue Chen; Qiantao Jiang; Yuming Wei; et al. (Euphytica, 2026)

Integrated gravity and landsat analyses for hydrothermal alteration and fault zone mapping in the lokop geothermal prospect, Indonesia - Faisal Abdullah; Muhammad Yanis; Muhammad Ridha Adhari; Dian Darisma; Gartika Satria Nugraha; Muzakir Zainal; Nazli Ismail (Earth Science Informatics, 2026)

Seasonal variation and source apportionment of heavy metals in the Jhelum river: Implications for water security - Muhammad Faisal; Feng Wu; Muhammad Waseem Boota; Shan-e-hyder Soomro; Muhammad Naeem; Yuzhong Zhang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

QSPR modeling of anti-COVID drugs using distance-based topological indices - Hafiz Muhammad Fraz; Kashif Ali; Muhammad Faisal Nadeem; Mingqiang Wang; Saurav Mallik (Next Research, 2026)

Artificial intelligence-driven metallogenic typing of pyrite from global ore systems - Muhammad Amar Gul; Asia Kanwal; Mohamed Faisal; Tehseen Zafar; Rizwan Sarwar Awan; Shamim Akhtar; Ibrar Khan; Xiaoyong Yang (Journal of Geochemical Exploration, 2026)

Red pepper seed protein isolate: Pulsed electric field assisted modification to improve its structural and functional properties - Murtaza Ali; Xin-An Zeng; Muhammad Faisal Manzoor; Isam A. Mohamed Ahmed; Muhammad Waseem (Innovative Food Science & Emerging Technologies, 2026)

Hydrogenation of CO2 to formate/formic acid over Pd/H-MOR - Faisal Irshad; Dan Zhang; Hamzah A.S.M. Yaseen; Xianming Zhu; Muhammad Chawla; Shengping Wang; Yongli Shen; Xinbin Ma (Chemical Engineering Journal, 2026)

Alginate-based biomaterials as versatile carriers for biomedical applications - Safaa Adim; Muhammad Faisal Afridi; Salwa El Baakili; Ahmed Fatimi; Latifa Bouissane (Carbohydrate Polymers, 2026)

Antagonistic and synergistic interactions between Bacillus and Pseudomonas in the rhizosphere: Mechanistic basis, ecological constraints, and applications in plant growth promotion and disease suppression - Muhammad Mubeen; Bushra Mumtaz; Muhammad Umar Shafiq; Phyu Shin Thant; Tahir Mahmood; Muhammad Arslan Mushtaq; Sazada Siddiqui; Faisal Zulfiqar; Anam Moosa (Physiological and Molecular Plant Pathology, 2026)

Harnessing the biocontrol potential of Trichoderma: Mechanisms, applications, and future prospects in sustainable crop protection - Muhammad Faiq Irfan; Amjad Ali; Rabia Noor; Aniqa Ijaz; Hamza Rafiq; Faisal Shafiq Mirza (Physiological and Molecular Plant Pathology, 2026)

Forecasting plastic waste collection in Bandung, Indonesia using ARIMA, LSTM, and prophet algorithm - Rhesa Muhammad Faisal; Olusola Olaitan Ayeleru; Helen Uchenna Modekwe; Ishmael Matala Ramatsa (Next Research, 2026)

Machine learning-based permeability prediction for CO₂ storage: A case study from the Petrel Sub-basin, Australia - Muhammad Faisal Waqar; Shengwen Qi; Songfeng Guo; Zan Wang; Bowen Zheng; Manawar Pervaiz (Geomechanics for Energy and the Environment, 2026)

Climatic suitability and geospatial assessment of Black Soldier Fly Larvae (BSFL) for sustainable waste management - Muhammad Salam; Sami Ullah; Fakhri Alam; Camila Rodríguez-Ortega; Samia Elouali; Viola Vambol; Shafi'u Adamu; Viviana Bolletta; Faisal Hayat; Zhiyong Han (Environmental Development, 2026)

Dopamine Receptor D2 gene Polymorphisms rs2005313, rs4274224, and rs4938019 in Pakistani Patients with Schizophrenia:a Diagnostic Tool for Schizophrenia - Ishrat Yaseen; Saleem Ahmad; Muhammad Ghalib; Muhammad Shahbaz Aslam; Rabbia Tariq; Osheen Sajjad; Faisal Yaseen (Journal of Molecular Neuroscience, 2026)

Linear parameter varying based adaptive model predictive control for power down regulation of floating offshore wind turbines in region–3 - Muhammad Sharjil; Muhammad Faisal Aftab (Ocean Engineering, 2026)

Recent developments in design and fabrication of ZIF-based materials for CO2 mitigation and environmental remediation - Hafsa Khalid; Aimon Saleem; Umer Younas; Parveen Akhter; Heena Ameen; Faisal Ali; M.I. Khan; Muhammad Pervaiz (Journal of Environmental Management, 2026)

Chitosan-crosslinked microwave-engineered biochar alleviates lead stress in Brassica napus by improving soil functioning and plant performance in Pb-contaminated soil - Fakhir Hannan; Yiwa Hu; Ahsan Ayyaz; Muhammad Iqbal; Muhammad Umair Yasin; Iram Batool; Juanjuan Li; Faisal Islam; Yasir Hamid; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Environmental Management, 2026)

Diesel engine performance enhancement using MXene nano-additives: An experimental study on efficiency and Pollutant Suppression - Mohd Danish; Sajid Ali; Syed Mohd Yahya; Rashid Ali; Suhaib Umer Ilyas; Sami Mansour Ghazali; Muhammad Faisal Rathore; Saeed Rubaiee (Fuel, 2026)

Artificial intelligence integrated in non-destructive technologies for monitoring food freshness: A review of next generation approach - Muhammad Waseem; Muhammad Rizwan Javed; Muhammad Faisal Manzoor; Xiuqi Xia; Yilei Huang; Xiaomei Chen (Food Research International, 2026)

Alleviation of salinity induced toxicity in quinoa (Chenopodium quinoa Willd.) through ascorbic acid application - Muhammad Faisal Maqsood; Tahira Fatima; Rehana Kanwal; Fozia Farhat; Muhammad Shahbaz; Muhammad Jamil; Saba Shafqat; Muhammad Asif; Muhammad Hamza Maqsood; Maryam Tariq; Usman Zulfiqar; Muhammad Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Green Synthesis of a ZnO@Sorghum Nano-Bioadsorbent for Enhanced Dye Wastewater Treatment - Muhammad Arslan Khalil; Bushra Sadia; Saima Noreen; Faisal Saeed Awan; Azeem Iqbal Khan; Muhammad Asif; Bilal Ahmad (Water, Air, & Soil Pollution, 2026)

Smart Wastewater Management: Data-Driven Prediction of Wastewater Using Optimized Learning Techniques - Ali Aldrees; Mohammad Jameel; Bilal Siddiq; Muhammad Hussain; Muhammad Faisal Javed; Furqan Ahmad (Water Conservation Science and Engineering, 2026)

Development and Performance Evaluation of an Indigenized Smart Field Lysimeter for Relative Crop Water-Use Assessment - Muhammad Faisal; Fiaz Hussain; Shoaib Rashid Saleem; Saliha Qamar (Water Conservation Science and Engineering, 2026)

Evaluation of Chitosan-Methotrexate Nanoparticles Loaded in Alginate Beads for Controlled Drug Delivery Against Breast Cancer - Abdullah Khan; Muhammad Fareed; Muhammad Khurshid Alam Shah; Asif Nawaz; Muhammad Faisal Shahzad; Muhammad Fauzi Abd Jalil; Zarif Mohamed Sofian; Muhammad Luqman Nordin (Journal of Pharmaceutical Innovation, 2026)

Probiotics unveiled: bridging general health benefits to the era of precision medicine - Mati Ullah; Muhammad Rizwan; Muhammad Ihtesham Waheed; Muhammad Shoaib Alam; Sami Ullah Jan; Ali Raza; Muhammad Faisal Shahid; Vivian Andoh; Yong Chen (World Journal of Microbiology and Biotechnology, 2026)

Petrogenesis and tectonic implications of the Late Palaeozoic Koga alkaline–carbonatite complex, NW Pakistan: insights from U–Pb geochronology, geochemistry, and Sr–Nd–C–O isotopes - Asad Khan; Zaheen Ullah; Huan Li; Shah Faisal; Delores M. Robinson; Muhammad Farhan; Nasir Ahmad (International Geology Review, 2026)

Global seroprevalence and epidemiological patterns of equine viral arteritis from 1968 to 2025: A systematic review and meta-analysis - Lintang Winantya Firdausy; Faisal Fikri; Arya Pradana Wicaksono; Salipudin Tasil Maslamama; Muhammad Thohawi Elziyad Purnama (Preventive Veterinary Medicine, 2026)

Nanoparticles in potato disease management: Applications, mechanisms, and future perspectives for sustainable crop production - Aneeza Ishfaq; Ishrat Bano; Irfan Haidri; Muhammad Shahid; Muhammad Sohail Akram; Muhammad Khubeb Ashfaq; Sabir Hussain; Tanvir Shahzad; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2026)

Detrital zircon geochronology and geochemistry of the Balochistan beach sediments, western Pakistan: Implications for provenance, palaeoweathering, and tectonic setting - Mohammad Naseer; Huan Li; Yasin Rahim; Mohamed Faisal; Yue Hou; Iqtidar Hussain; Shafi Muhammad (Journal of Asian Earth Sciences, 2026)

Erratum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdual Waheed Rabbni; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Corrigendum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdul Waheed Rabbani; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Enhancing proton conduction through SLZO-LCO pn-Junction heterostructures in semiconductor ionic membrane fuel cells - Yuqi Zhou; Touseef Ahmad; Kashf Zman; Hafsa Mansha; Muhammad Faisal Anwar; Peng Zhou; Lian Chen; Haijun Wang; Yuran Qi; Yuzheng Lu (Fuel, 2026)

Performance evaluation of sustainable concrete incorporating mineral fillers: experimental insights and predictive modeling using advanced machine learning - Maaz Khan; Muhammad Faisal Javed; Usama Asif; Hisham Alabduljabbar (Innovative Infrastructure Solutions, 2026)

Olanzapine for chemotherapy-induced nausea and vomiting in breast cancer: a systematic review and meta-analysis of prospective randomised controlled trials - Syeda Masooma Jafri; Muhammad Shahzou Shah; Javeria Nawaz; Zainab Ali Siddiqui; Minhal Faisal; Abia Khalid Mir; Rana Taha Jamal (European Journal of Clinical Pharmacology, 2026)

Global prevalence and epidemiological determinants of African horse sickness: A systematic review and meta-analysis - Muhammad Thohawi Elziyad Purnama; Lintang Winantya Firdausy; Faisal Fikri; Arya Pradana Wicaksono; Salipudin Tasil Maslamama; Lailia Dwi Kusuma Wardhani (The Veterinary Journal, 2026)

Synergistic effects of pulsed electric field and ultrasound on microstructure and bioactive properties of fresh and old ginger juice - Zhong Han; Wenhao Xiao; Ji Ma; Muhammad Mohsin Raza; Xin-An Zeng; Muhammad Faisal Manzoor; Muhammad Talha Afraz (Journal of Food Engineering, 2026)

Retraction notice to “Dual Z-scheme core-shell PANI-CeO2-Fe2O3-NiO heterostructured nanocomposite for dyes remediation under sunlight and bacterial disinfection” [Environ. Res. 215 (2022) 114140] - Faisal Mukhtar; Tauseef Munawar; Muhammad Shahid Nadeem; Muhammad Naveed ur Rehman; Shoukat Alim Khan; Muammer Koc; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Research, 2026)

Retraction notice to “Boosted charge separation via Ce2S3 over dual Z-scheme ZnO–Ce2S3–MnO2 core double-shell nanocomposite for the degradation of diverse dye pollutants” [Environ. Res. 251 (2024) 118675] - Tauseef Munawar; Taghrid S. Alomar; Chang-Feng Yan; Saman Fatima; Faisal Mukhtar; Muhammad Shahid Nadeem; Najla AlMasoud; Shoukat Alim Khan; Muammer Koc; Yahya Zakaria; Faisal Iqbal (Environmental Research, 2026)

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Efficacy of Vachellia nilotica Extract-coated Urea in Maize: Field Performance and Phytochemical Basis of Urease Inhibition - Rashid Mahmood; Hina Jabeen; Muhammad Ajmal Rana; Faisal Nadeem; Ejaz Ahmed; Muhammad Bilal Chattha (Journal of Soil Science and Plant Nutrition, 2026)

Thiourea Mediated Improvement of Drought Stress in Maize (Zea Mays L.): Unrevealing Morpho-Physiological, Biochemical, and Root Attributes - Arslan Haider; Ejaz Ahmad Waraich; Surriya Bibi; Tahrim Ramzan; Muhammad Ahmad; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Mesenchymal stem cell-based therapeutic strategies for female infertility: current evidence and emerging targeting approaches - Muhammad Sajid; Faiz-ul Hassan; Atique Ahmed Behan; Fethi Ahmet Ozdemir; Faisal Siddique; Sarfraz Ali Fazlani; Muhammad Asif Arain; Muhammad Saif-ur Rehman (Biotechnology Letters, 2026)

Geospatial analysis of surface urban heat island dynamics and land use changes in Pakistan using multi-spectral indices - Awais Ali; Bilal Hussain; Muhammad Naveed; Bader Alshehri; Abdul Ghafoor; Zeeshan Zafar; Faisal Sultan Qadri (Advances in Space Research, 2026)

Phylogenetic and genome-wide analysis of codon usage reveals geographic and host-specific adaptation in Vaccinia virus - Hafsa Iqbal; Faisal Ahmad; Sajjad Ahmad; Iftikhar Ahmad; Muhammad Yar Sobhan Qadir; Ali Khalid; Zurva Ashraf; Zohra Ahmad; Ferjeni Zouidi (Archives of Virology, 2026)

Habitat connectivity and physicochemical gradients shape nekton assemblage across the seagrass-mangrove continuum in Bangka Island, Indonesia - Ahmad Romdon; Agung Yunanto; Tri Handayani; Frida Sidik; Ernawati Widyastuti; Faisal Hamzah; Jemi Ferizal; Wahyu Adi; Chao Fang; Jianguo Du; Annisa Fitri; Jordi Anugrah Lumban Raja; et al. (Aquatic Ecology, 2026)

Cover Image - Faisal Ahmad Lodhi; Fahim Ullah Khan; Aabid Ullah Khan; Jae‐Seong Lee; Muhammad Abbas; Hanafiah Fazhan; Khor Waiho; Menghong Hu; Youji Wang (Reviews in Aquaculture, 2026)
The cover image is based on the article Multi‐Stressor Responses in Marine Bivalves: Integrating Climate Change, Pollutants, and Microbiome Shifts for Aquaculture Resilience by Faisal Ahmad Lodhi et al., https://doi.org/10.1111/raq.70169 . image

Multi‐Stressor Responses in Marine Bivalves: Integrating Climate Change, Pollutants, and Microbiome Shifts for Aquaculture Resilience - Faisal Ahmad Lodhi; Fahim Ullah Khan; Aabid Ullah Khan; Jae‐Seong Lee; Muhammad Abbas; Hanafiah Fazhan; Khor Waiho; Menghong Hu; Youji Wang (Reviews in Aquaculture, 2026)
Marine bivalves play pivotal ecological and economic roles but are increasingly challenged by multiple environmental stressors. Although there is extensive research on the effects of individual stressors, a comprehensive review is needed to synthesize current evidence and clarify how multiple interacting stressors collectively affect the physiology and resilience of marine bivalves. This review integrates evidence from 2010 to 2025, encompassing 178 peer‐reviewed studies emphasizing the combined and interactive impacts of climate change drivers (warming, hypoxia, salinity, and ocean acidification), pollutants (heavy metals, persistent organic pollutants, endocrine‐disrupting chemicals, antibiotics, nanoparticles, microplastics), and microbiome shifts on future aquaculture resilience. Literature was systematically retrieved from Web of Science, Scopus, PubMed, and Google Scholar in accordance with PRISMA 2020 guidelines. Bibliometric mapping (VOSviewer 1.6.20) revealed a rapid growth in research after 2018, characterized by studies on Mytilus , Crassostrea , and Ruditapes . A systematic evaluation of recent evidence was conducted, combining data from physiological, molecular, and microbial studies, with particular attention to implications for aquaculture. The analysis reveals that stressors rarely act alone. Instead, their cumulative and interactive effects cause oxidative stress, disrupted energy allocation, destabilized host‐microbe relationships, lowered tolerance thresholds, and other eco‐physiological consequences. These results highlight the vulnerability of bivalve populations to rapid coastal urbanization, declining water quality, and sediment contamination. The review concludes that resilience can be enhanced through selective breeding for stress‐tolerant genotypes, integrated monitoring of pollutants and microbial indicators, and multi‐omics approaches to guide adaptive aquaculture management.

A parsimonius agroclimatic methodology to assess the hydrological sustainability of agriculture in the Mediterranean semiarid climate - Stefano Barontini; Martina Greta Caffi; Muhammad Faisal Hanif; Elpida Kolokytha; Dimitrios Malamataris; Hiba Mohammad; Marco Peli (Hydrological Sciences Journal, 2026)

Five-year evidence synthesis of African swine fever in domestic pigs in Southeast Asia: A systematic review and meta-analysis - Lintang Winantya Firdausy; Faisal Fikri; Salipudin Tasil Maslamama; Muhammad Thohawi Elziyad Purnama (Research in Veterinary Science, 2026)

Radiological contamination in soils near the world's largest rare earth minerals producing region and their impacts on human health: A summary analysis - Amir Hamza; Faisal Khan; Javed Nawab; Junaid Ghani; Sajid Ali; Yaseen Laghari; Luo Xin; Niaz Muhammad; Jing Cui; Zhenggui Wei (Journal of Environmental Radioactivity, 2026)

Characterization of stable grain protein content loci on chromosome 6D without adverse effect on yield traits in bread wheat - Hang Liu; Chao Wang; Jiating Chen; Huaping Tang; Tongzhu Wang; Md Nahibuzzaman Lohani; Hafiz Muhammad Faisal Umer; Muhammad Junaid Jalil; Haopeng Zhang; Xia Yang; Qiang Xu; Jian Ma; et al. (Theoretical and Applied Genetics, 2026)

Correction to: Sedative effects of physcion and its modulatory interaction with diazepam: in vivo and in silico evaluation - Md. Shadin; Md. Shimul Bhuia; Mohammed Alfaifi; Abdullah H. Altemani; Faisal H. Altemani; Faisal Alsenani; Raihan Chowdhury; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sedative effects of physcion and its modulatory interaction with diazepam: in vivo and in silico evaluation - Md. Shadin; Md. Shimul Bhuia; Mohammed Alfaifi; Abdullah H. Altemani; Faisal H. Altemani; Faisal Alsenani; Raihan Chowdhury; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unraveling the synergistic effects of Bacillus cereus and different concentrations of silicon nanoparticles on wheat under rain-fed conditions of Pakistan - Muhammad Umer; Kahkashan Perveen; Faheema Khan; Jayanthi Barasarathi; Naeem Khan; Nageen Bostan; Summiya Faisal; Zainab Asif; Noshin Ilyas (Environmental Geochemistry and Health, 2026)

A weighted ensemble DL framework for granular RPV inventory and energy yield analysis in Pakistan - Muhammad Kamran Lodhi; Yumin Tan; Yang Li; Faisal Mumtaz; Shahid Naeem (Remote Sensing Applications: Society and Environment, 2026)

Retraction notice to “Borage leaf extract improves the vase life of cut gladiolus flowers by delaying the senescence process and reducing water stress” [Postharvest Biol. Technol. 210 (2024) 112766] - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Anastasios Darras; Mohamed S. Sheteiwy; Baber Ali; Muhammad Ahsan Altaf; Walid Soufan; Ayman El Sabagh (Postharvest Biology and Technology, 2026)

Social media sentiment exposure to climate-induced floods and risk responses to the 2022 flood in Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Jiali Guo; Caihong Hu; Muhammad Faisal; Junaid Abdul Wahid; Gul-e-Zehra Soomro (Journal of Environmental Management, 2026)

Sodium cyclamate alters cardiac homeostasis via immunoinflammatory signaling modulation: A multi-biomarkers and in-silico evaluation - Muhammad Faisal Hayat; Abdulaziz Saleh Alkhoshaiban; Hesham M. Hassan; Syeda Sania Zahara; Ali Akbar; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani (Journal of Environmental Sciences, 2026)

Techno-economic assessment of field-scale storage for liquid organic hydrogen carriers: dual benefits of energy storage & incremental oil recovery - Zeeshan Tariq; Mutaz AlSubhi; Muhammad Ali; Narendra Kumar; Faisal Alissa; Abdulwahab Ghamdi; Hussein Hoteit (Fuel, 2026)

Photo-activated defect engineering unlocks high-performance proton transport in garnet electrolytes - Bushra Bibi; Atif Nazar; Muhammad Yousaf; Tanveer Farid; Rizwan Raza; Syed Asad Abbas Bukhari; Muhammad Faisal Anawar; Kashif Nazar; Hafsa Mansha; Yuzheng Lu; Bin Zhu (Chemical Engineering Journal, 2026)

Ferruginol as multifunctional abietane diterpenoid-comprehensive pharmacological evaluation and computational drug discovery insight - Iqra Farzeen; Maryam Batool; Zunaira Jaan; Saira Saeed; Muhammad Muzammil Nazir; Shahla Faisal; Asma Ashraf (Phytochemistry Reviews, 2026)

First Report on Phytochemical Profiling and Biological Activities of Anthemis cotula L. Flowers - Saqib Ullah; Muhammad Aaqil Khan; Afnan M. Alnajeebi; Faten Zubair Filimban; Faisal Alsenani; Sher Wali (Journal of Pharmaceutical Innovation, 2026)

Retraction Note: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2026)

Techno-economic analysis of emerging energy generation processes and technologies for climate change mitigation - M. Imran Khan; Muhammad Asif; Faisal Asfand (Process Safety and Environmental Protection, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Synergistic effect of Clupea harengus by-product hydrolysates and kappa carrageenan mixture on oxidation prompted structural alterations in Clupea harengus proteins during frozen temperature variations - Noman Walayat; Piotr Kulawik; Asad Nawaz; Isam A. Mohamed Ahmed; Muhammad Faisal Manzoor; Zhucheng Su; Ran Wei (Food Hydrocolloids, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Integrative analysis of rhizosphere metabolomics and root anatomical adaptations in wheat under drought stress: comparative insights from DH-11 and PK-13 - Sohail Ahmed; Muhammad Kaleem Samma; Faisal Mehdi; Kamran Yaqoub; Manzer H. Siddiqui; Amna Jabbar Siddiqui; Syed Ghulam Musharraf; Saddia Galani; Zubia Rashid; Hania Ahmed (Physiology and Molecular Biology of Plants, 2026)

A scoping review of climate vulnerability indicators: implications for neighborhood-level vulnerability - Muhammad Faisal Shehzad; Joonsoo Sean Lyeo; Nabil Bleibel; Sarah R. Haines; Nicholas D. Spence; Helen Stopps (Climatic Change, 2026)

Integrative Taxonomic Study Reveals Tricholomopsis habibii sp. nov. from Swat District, Khyber Pakhtunkhwa, Pakistan - Zia Ullah; Sana Jabeen; Muhammad Faisal; Fauzia Razzaq; Hira Ijaz; Abdul Nasir Khalid (New Zealand Journal of Botany, 2026)
Tricholomopsis habibii sp. nov. has been described and illustrated, based on collections made from the Swat District, Khyber Pakhtunkhwa, Pakistan. This species differs from Tricholomopsis badinensis by its large (70–100 mm), dull brown to pale yellow pileus with a flattened umbo, lacrymoid to ellipsoid, oblong in side view basidiospores, and small (39.9–51.7 × 6.9–8. μm) cheilocystidia. The nuclear ribosomal internal transcribed spacer region and a portion of the nuclear ribosomal large subunit (28S) of this species were sequenced and analyzed which confirmed the identity of T. habibii as a new taxon.

Fiscal and monetary policy for green growth: the role of institutional quality in South Asia - Rabia Nazir; Seemab Gillani; Muhammad Nouman Shafiq; Muhammad Junaid Nasrullah; Muhammad Faisal Shahzad (Environment, Development and Sustainability, 2026)

Nepetin attenuates sertraline-induced cardiac dysfunction by modulating notch signaling, oxidative stress, and inflammation: Echocardiographic and histological evidence - Hassan M. Otifi; Muhammad Faisal Hayat; Aqsa Bibi; Hesham M. Hassan; Ahmed Al-Emam (Tissue and Cell, 2026)

Optimizing category-based statistical metrics for selecting global climate models in rainfall projections for Peninsular Malaysia - Zulfaqar Sa’adi; Dauda Pius Awhari; Ricky Anak Kemarau; Zainura Zainon Noor; Zhang Taining; Mohamad Faizal Ahmad; Abdalmaged Salem; Gunarangini Muniandy; Mohammed Faisal Mohammed Dafalla; Wimbi Apriwanda Nursiwan; Muhammad Reza Agraha Maha; Ariani Dwi Astuti; et al. (Theoretical and Applied Climatology, 2026)
Rainfall projections are crucial for climate impact assessments and water resource management, especially in regions like Peninsular Malaysia (PM), where climate variability has a profound effect on socioeconomic and environmental systems. This study aims to optimize category-based statistical metrics, namely, error, efficiency, correlation, composite, and others, to reduce redundancy and identify the most reliable global climate models (GCMs) for improving rainfall projection accuracy in PM. Using CHIRPS daily rainfall data and GCM outputs from the Coupled Model Intercomparison Project Phase 6 (CMIP6), a multi-filtration approach was employed to rank GCM performance based on optimized metrics. The selected metrics span five categories, namely, 7 error metrics, 5 efficiency metrics, 3 correlation metrics, 2 composite metrics, and 5 other metrics, to address a broad range of evaluation needs, ensuring a rigorous and non-redundant assessment of GCMs. A systematic selection of GCM evaluation metrics reduced redundancy by up to 64%, retaining eight key metrics. Principal component analysis (PCA) confirmed these metrics as the most representative, with the first two principal components (PCs) capturing 95.5–100% of the total variance. Using compromise programming index (CPI) and Fisher-Jenks classification, five top-performing GCMs, namely, TaiESM1 (0.5507), CMCC-ESM2 (0.6753), MRI-ESM2-0 (0.7473), CMCC-CM2-SR5 (0.8402), and EC-Earth3-Veg (1.0233), were identified, with TaiESM1 (overlap efficiency, OVL = 0.96) and CMCC-ESM2 (OVL = 0.91) most closely replicating CHIRPS rainfall, making them highly recommended for reliable climate projections. The study concludes that this optimization framework significantly enhances rainfall projection reliability, thereby supporting better-informed decision-making in climate adaptation and water resource planning. Furthermore, the methodology provides a replicable approach for improving GCM selection, particularly in regions with complex climate dynamics, advancing climate modeling for sustainable development planning.

Zinc-regulated growth, chlorophyll, and antioxidant activity drive biofortification in rice varieties - Hafiza Ammara; Asma Zulfiqar; Ammara Saleem; Rehana Sardar; Usman Zulfiqar; Muhammad Aown Sammar Raza; Muhammad Faisal Maqsood; Hossam S. El-Beltagi; Mashael Daghash Alqahtani (BioMetals, 2026)

Virophages: mechanisms, ecological Roles, and therapeutic potential in combating giant virus infections - Muhammad Talha; Mehak Faisal; Amna Mujtaba; Amna Amjad; Nouraiz Abbas; Laiba Shamim; Fakhar e Mahin; Muammar Hassan; Muhammad Daim Hassan; Muhammad Abdur Rehman Awaisi (Archives of Microbiology, 2026)

Computational prediction of thermomechanical properties in ionic liquid-modified MWCNT/carbon fiber composites - Bilal Ghafoor; Faisal Ghafoor; You Jinglin; Muhammad Shakeel Ahmed; Masood Ahmed; Silvia Tamborim; Sandro Campos Amico; Henri Stephan Schrekker (Next Research, 2026)

Sulfoxaflor provokes progressive myocardial injury by disrupting HIF-1α/VEGFA signaling, redox balance, and inflammation: A comprehensive biochemical, echocardiographic, and histopathological approach - Yingying Dong; Salim Jamil; Mahmoud El Safadi; Ali Akbar; Muhammad Faisal Hayat; Ahmed Al-Emam; Hesham M. Hassan (Journal of Environmental Sciences, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Metal-organic framework-derived defect-enriched bimetallic Cerium/Manganese oxide nanocomposite with carbon for boosted water electrolysis and supercapacitor applications - Tauseef Munawar; Ambreen Bashir; Sonia Sardar; Muhammad Rafaqat; Guo Changqing; Mostafa A. Ismail; Shoukat Alim Khan; Muammer Koc; Suleyman I. Allakhverdiev; Faisal Iqbal; Chang-Feng Yan (Fuel, 2026)

Intensification of plasma process for the decomposition of p-xylene as a tar model compound to minimize the unwanted byproduct formation - Faisal Saleem; Muhammad Farooq; Azam Saeed; Shehzad Mustafa; Zaeem Bin Babar; Abdul Rehman; Syed Waqas Ahmad; Kui zhang; Adam Harvey (Fuel, 2026)

National-scale land suitability assessment for eucalyptus plantation in Pakistan using analytic hierarchy process (AHP) and geospatial modeling - Faisal Khalid; Sami Ullah; Muhammad Shafique; Majid Hussain (Forest Ecology and Management, 2026)

Macroscale spatiotemporal variability of Beryllium-7 and Lead-212 in surface air driven by meteorological factors - Faisal Izwan Abdul Rashid; Mohd Idzat Idris; Irman Abdul Rahman; Muhammad Rawi Mohamed Zin (Environmental Research, 2026)

Repurposing fluoroquinolones as cancer chemosensitizers: a way to overcome cancer therapeutic bottleneck - Muhammad Ishaq; Erum Zafar; Muhammad Faisal Maqbool; Muhammad Mansha; Muhammad Khan; Yongming Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Isolation, Characterization, and Modes of Action of Antifungal Compounds from Rhizomes of Dryopteris nigropaleacea - Faisal I. Jafri; Muhammad Akbar; Yasir Nazir; Amna Khalil; Khizar H. Bhatti; Anna Andolfi; Muhammad W. Mazhar; Shoaib Ashiq (Current Microbiology, 2026)

An integrated geohazard assessment approach for sustainable small hydropower projects: A case study from the Western Himalayan Syntaxes, Northern Pakistan - Khan Zada; Shengwen Qi; Yongchao Li; Weiwei Zhu; Zan Wang; Bowen Zheng; Songfeng Guo; Muhammad Faisal Waqar; Syed Zohaib Hassan Bukhari (Bulletin of Engineering Geology and the Environment, 2026)

NMR-based metabolic profiling and antioxidant activity of Eleutherine bulbosa bulb ethanol extract - Islamudin Ahmad; Lizma Febrina; Baso Didik Hikmawan; Junaidin Junaidin; Herman Herman; Muhammad Faisal; Erwin Samsul; Iswahyudi Iswahyudi; Arsyik Ibrahim; Reza Yuridian Purwoko; Tia Okselni; Marissa Angelina; et al. (Natural Product Research, 2025)

Synergistic effects of selected ethnomedicinal plants with Metronidazole against resistant H. Pylori, and their urease inhibition mechanism - Sania Atta; Marya Nawaz Malik; Muhammad Tahir Aqeel; Iffat Naz; Nadeem Irshad; Sadaf Naz; Nadeem ul Hassan Khan; Faisal Rasheed; Humaira Fatima (South African Journal of Botany, 2025)

Legal effectiveness of business contracts in tin mining: Socio-legal and governance challenges in corporate–community relations in Indonesia - Derita Prapti Rahayu; Muhammad Rustamaji; Faisal Faisal; Rafiqa Sari (Resources Policy, 2025)

Molybdenum induces hepatic impairments via dysregulating NLRP3, JAK1/STAT3 and NF-κB pathways: A dose dependent toxicity assessment - Mahmoud El Safadi; Abdulaziz Saleh Alkhoshaiban; Muhammad Faisal Hayat; Syeda Sania Zahara; Ali Akbar; Maha A. Al-Aream; Salim Jamil; Hesham M. Hassan (Journal of Trace Elements in Medicine and Biology, 2025)

Cardioprotective potential of azaleatin against sodium arsenite instigated sub-chronic cardiotoxicity via targeting TLR4/MyD88, JAK1/STAT3, and NF-κB in Sprague Dawley rats - Hesham M. Hassan; Aqsa Bibi; Muhammad Faisal Hayat; Khalid J. Alzahrani; Fuad M. Alzahrani; Meshari A. Alsuwat; Maha A. Al-Aream (Journal of Trace Elements in Medicine and Biology, 2025)

Therapeutic potential of spinacetin against cadmium-exacerbated hepatic ischemia/reperfusion injury via regulating AMPK/SIRT1/PGC-1α and NF-κB pathway - Aqsa Bibi; Hong-xing Zhang; Muhammad Faisal Hayat; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani (Journal of Trace Elements in Medicine and Biology, 2025)

Air quality management from the lens of leveraging social media data and machine learning algorithm for hazard zoning-real-time air pollution detection in urban cities under changing climate - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Gul-e-Zehra Soomro; Muhammad Faisal; Caihong Hu; Junaid Abdul Wahid; Jiali Guo (Journal of Environmental Management, 2025)

Synergies and struggles: Water security and climate action in South Asia’s quest for SDG 6 and SDG 13 - Faisal Baig; Assaad Kassem; Md. Zishan Akhter; Saifudeen Kabeer; Muhammad Abrar Faiz; Mirza Farrukh Baig; Mohsen Sherif (Gondwana Research, 2025)

Solid phase microextraction of chlorpyrifos residues in food samples using polyacrylamide@MOF/MXene composite - Sumaira Sabir; Nadeem Raza; Muhammad Hayat; Suryyia Manzoor; Faryal Aftab; Lilia Basilio de Caland; Muhammad Imran Khan; Ahmed Yar; Faisal K. Algethami; Mostafa E. Salem; Anis Ahmad Chaudhary; Muhammad Naeem Ashiq (Food Chemistry, 2025)

Impact of Tannery Effluents on Groundwater Quality and Human Health in Kasur, Pakistan - Mohammad Salman Faisal; Muhammad Awais; Rohina Bashir; Muhammad Bilal Shakoor; Rizwan Aziz; Muhammad Rizwan; Affaq Ali; Simal Akhtar; Noor Fatima (Water, Air, & Soil Pollution, 2025)

Biomonitoring Vehicular Pollution Using Naturally Occurring Indicator Species Ricinus communis L. (Euphorbiaceae) Along Roadways - Muhammad Faisal Gul; Ummar Iqbal; Muhammad Sharif; Nargis Naz; Farooq Ahmad (Water, Air, & Soil Pollution, 2025)

Unlocking the role of transcription activator-like effector nuclease (TALENs) and zinc finger nuclease (ZFN) in the treatment of HIV - Akmal Zubair; Muhammad Ali; Faisal Ahmad; Saed Ayidh Althobaiti (Molecular Biology Reports, 2025)

Green Synthesis, Characterization, and Effect of Zinc Oxide Nanoparticles on Wheat (Triticum Aestivum L.) Under Cadmium Stress - Aqsa Khan; Samina Jam Nazeer Ahmad; Muhammad Jafir; Adeel Ahmad; Muhammad Irfan; Muhammad Qasim; Jam Nazeer Ahmad; Muhammad Azeem Sabir; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Flavones-Fortified Biochar Enhances Barley (Hordeum Vulgare L.) Growth and Productivity by Ameliorating Cadmium and Copper Toxicity - Ghulam Murtaza; Muhammad Bilawal Junaid; Faisal Mahmood; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Alanoud T. Alfagham; Javed Iqbal; Gang Deng; Zeeshan Ahmed; Trobjon Makhkamov; Lala Gurbanova; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Unveiling the synergistic potential of nucleopolyhedroviruses and insecticides against Helicoverpa armigera Hübner (Lepidoptera; Noctuidae) - Muhammad Jafir; Jam Nazeer Ahmad; Samina Tanwir; Muzamil Abbas; Faisal Hafeez; Muhammad Azeem Sabirb; Abdul Rehman; Abdulrahman S. Aldawood (Journal of Plant Diseases and Protection, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Dynamic Testing Methods and Failure Properties of Rocks: A Comprehensive Review - Muhammad Faisal Waqar; Shengwen Qi; Bowen Zheng; Songfeng Guo (Rock Mechanics and Rock Engineering, 2025)

Chitosan induces water deficit stress tolerance in Gladiolus grandiflorus via regulating water relations, gaseous exchange traits, and antioxidative defense - Muhammad Rizwan; Gulzar Akhtar; Muhammad Asif Shehzad; Salman Aloufi; Suliman Mohammed Suliman Alghanem; Faisal Zulfiqar; M. Nasir Khan; Özhan Şimşek; Fahad Al-Asmari; Mehmet Tütüncü; Tolga İzgü; Lala Gurbanova (Plant Biosystems, 2025)

Neuroprotective potential of fortunellin against titanium dioxide nanoparticles induced neurotoxicity via regulating NLRP3, HMGB1/RAGE, and NF-κB pathway: A biochemical, histological and in-silico experimentation - Abdulaziz Saleh Alkhoshaiban; Muhammad Faisal Hayat; Mahmoud El Safadi; Hesham M. Hassan; Ali Akbar; Syeda Sania Zahara; Ahmed Al-Emam (Toxicon, 2025)

Casuarinin modulates renin-angiotensin-aldosterone system to counter ephedrine-induced myocardial damage in rats - Hesham M. Hassan; Muhammad Faisal Hayat; Ali Akbar; Azka Zafar; Khalid J. Alzahrani; Fuad M. Alzahrani; Abrar Aljohani (Toxicon, 2025)

Harnessing metal-organic frameworks (MOFs) in agriculture: Mechanisms and application strategies for management of plant diseases - Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Yumna Rasheed; Faizah Amer Altihani; Mohamed Hashem; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2025)

Seismic fragility and resilience assessment of pile-supported wharves with isolation systems in liquefied soil - Yao Cui; Sami Ur Rehman; Zhuoxin Wang; Ying Cui; Abid Ali; Muhammad Shameer Faisal (Ocean Engineering, 2025)

Bridging the resolution gap: Machine learning for local-scale groundwater drought monitoring in Punjab, Pakistan - Fahimeh Youssefi; Shoaib Ali; Behnam Khorrami; Mohammad Mohsin Khan; Muhammad Jehanzaib; Talha Mahmood; Zhiming Han; Wu Haotian; Muhammad Faisal (Groundwater for Sustainable Development, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Sustainable biodiesel production from non-food biomass of Cucumis prophetarum via waste peel-based phyto-nanocomposite in membrane reactor: An innovative outlay for waste management and circular bioeconomy - Maria Ameen; Mushtaq Ahmad; Muhammad Zafar; Balal Yousaf; Muhammad Faisal Amin; Iftikhar Ahmed; Shabir Ahmad (Biomass and Bioenergy, 2025)

Impact of in-ovo dichromatic lights on embryonic growth, hatching performance and welfare traits in commercial layers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Saima; Hai Lin (Tropical Animal Health and Production, 2025)

Replacement of crop-residue silage for corn silage in feedlot buffalo - Muhammad Iqbal Anjum; Thiwakorn Ampapon; Shahbaz Javaid; Faisal Ashfaq; Metha Wanapat (Tropical Animal Health and Production, 2025)

Oleuropein modulates anti-inflammatory activity of celecoxib and ketoprofen through cyclooxygenase pathway: in vivo, in silico and pharmacokinetics approaches - Nishat Jahan; Manoj Mandal; Imam Hossen Rakib; Md. Sakib Al Hasan; Emon Mia; Noshin Tasnim Yana; Mohammed Alfaifi; Faisal H. Altemani; Rakib Hossan; Umme Habiba Sumaya; Ali Mohamod Wasaf Hasan; Md. Abu Sayeed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Wooden ash based nylon fiber reinforced concrete: experimental study on concrete strength properties - Muhammad Sheraz; Qiang Yuan; Muhammad Alam; Muhammad Faisal Javed (Innovative Infrastructure Solutions, 2025)

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

Spatio-temporal variability study of Shigar Basin Glaciers, Central Karakoram Region, Pakistan - Salman Mustafa; Faisal Rehman; Adnan Shafiq Rana; Tahir Azeem; Omar Riaz; Muhammad Fahad Ullah; Jamil Siddique; Faisal Rehman (Environmental Monitoring and Assessment, 2025)

Combined physiological effects of differentially charged nanoplastics and ocean acidification on the mussel Mytilus coruscus - Mojiang Zhang; Menghong Hu; Xinyi Li; Khor Waiho; Shihan Xu; Zeyu Song; Muhammad Faisal Khalil; Youji Wang (Marine Pollution Bulletin, 2025)

Syringetin ameliorates thallium sulphate induced renal dysfunction via regulating Nrf2/Keap-1, TLR4/HMGB1/RAGE and NF-κB pathway - Hassan M. Otifi; Muhammad Faisal Hayat; Ali Akbar; Syeda Sania Zahara; Khalid J. Alzahrani; Fuad M. Alzahrani; Khalaf F. Alsharif (Tissue and Cell, 2025)

Pinobanksin ameliorates perfluorooctane sulfonate-evoked cardiotoxicity via targeting Nrf-2/Keap-1, oxidative damage and inflammation in Sprague Dawley rats - Maryam Javed; Quratulann Sattar; Muhammad Faisal Hayat; Hamida Hamdi; Muhammad Zaid Salar (Tissue and Cell, 2025)

Depositional age and provenance of the Maziping Group, South China: Evidence from detrital zircon U–Pb dating and whole-rock geochemistry - Yasin Rahim; Huan Li; Thomas J. Algeo; Weidong Ren; Annan Guan; Mohammad Naseer; Zaheen Ullah; Asad Khan; Muhammad Yaseen; Mohamed Faisal (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Nano zero-valent iron engineered with microwave-prepared biochar for improved nickel immobilization in contaminated soil and growth of oil crop (Brassica napus) - Fakhir Hannan; Muhammad Ahsan Farooq; Ahsan Ayyaz; Muhammad Iqbal; Zaid Ulhassan; Kangni Zhang; Faisal Islam; Juanjuan Li; Iram Batool; Weijun Zhou (Journal of Environmental Chemical Engineering, 2025)

Low-temperature on-board hydrogen production using a novel hollow fibre-based packed bed reactor - Claire Leishman; Yuxiang Liu; Muhammad Akmal Bin Mohd Faisal; Kang Li; Francisco R. García-García (Chemical Engineering Journal, 2025)

Ter-polymeric Cytocompatible Hydrogels Based on Sodium Alginate with Pectin and Acrylic Acid for Controlled Loxoprofen Sodium Oral Delivery; In vitro and In vivo Evaluation - Samiullah Khan; Abdur Rehman; Syed Faisal Badshah; Muhammad Saad (Journal of Pharmaceutical Innovation, 2025)

Evaluating Tunnel Squeezing in the Lawi Hydropower Project, Chitral, Pakistan: Geological and Empirical Perspectives - Muhammad Tariq Niaz; Waqas Ahmed; Shah Faisal Khattak; Jehanzeb Khan; Luqman Ahmad; Ihtisham Islam; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Potential toxicological assessment of 4-Methylimidazole (4-MEI) in Ctenopharyngodon idella; LC50 determination, acute and sublethal effects on physiological, immunological, and histopathological indicators - Muhib Zaman; Amina Zuberi; Waqar Younas; Muhammad Noorullah; Faisal Ahmad Lodhi; Adnan Khan (Fish Physiology and Biochemistry, 2025)

Analysis of Ancient Rongcharong Landslide Dam Failure Events in the Suwalong Reach of the Upper Reaches of the Jinsha River - Yongchao Li; Songfeng Guo; Bowen Zheng; Yu Zou; Shengyuan Song; Yiwei Zhang; Jianhua Yan; Muhammad Faisal Waqar; Khan Zada; Shengwen Qi; Jianping Chen (Journal of Earth Science, 2025)

Antiemetic Efficacy of Nodakenin Through Muscarinic, Dopaminergic, and Serotonergic Receptor Modulation: Combined Experimental and Computational Approach - Towfiqur Rahman; Feroz Khan Nun; Tawfik Rakaiyat Ripu; Md. Sakib Al Hasan; Md. Shakil Ahmmed; Mohammed Alfaifi; Faisal H. Altemani; Abdullah H. Altemani; Imam Hossen Rakib; Emon Mia; Md. Shimul Bhuia; Muhammad Torequl Islam (Cell Biochemistry and Biophysics, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Petrological and Re-Os isotopic constraints on the origin of chromitites and peridotites of the late cretaceous Waziristan ophiolite, western Pakistan: implications for subduction initiation - Zaheen Ullah; Asad Khan; Huan Li; Scott A. Whattam; Muhammad Tahir Shah; Liaqat Ali; Shah Faisal; Tehseen Zafar; Muhammad Farhan; Shuja Ullah; Syed Tanvir Shah; Zahid Hussain; et al. (International Geology Review, 2025)

Dynamic modeling and optimal control schemes for an offshore-wind powered direct air capture system with energy storage options - Muhammad Faisal Shehzad; Haris Ishaq; Curran Crawfrod (Science of The Total Environment, 2025)

Detection of genes encoding for absorption of hydrocarbons degradation by bacteria isolated from Antarctica, Malaysia, and Indonesia - Faisal Allafi; Muhammad Ridwan; Peter Convey; Dani Wijaya; Faradina Merican; Japareng Lalung (Next Research, 2025)

Roles of Fox gene in the development and reproduction of diamondback moth - Anam Noreen Abbas; Mubashir Tariq; Faisal Munir; Uroosa Zaheer; Ibrahim Adam; Muhammad Asad; Guang Yang (Journal of Insect Physiology, 2025)

Bridging sustainable finance, AI, and clean technology amid economic shocks: How are they connected in median and extreme conditions? - Sinda Hadhri; Faisal Nazir Zargar; Muhammad Abubakr Naeem; Faten Chibani (Journal of Environmental Management, 2025)

Enhancing agricultural sustainability through the combined use of bio-slurry and chemical fertilizers: Insights from field trials in pea and radish - Abdul Baseer Khan; Matiullah Khan; Taqi Raza; Malik Badshah; Muhammad Ishtiaq Ali; Faisal Jan; Asif Jamal; Zaixing Huang (Bioresource Technology Reports, 2025)

Retraction Note: Assessment of antiarthritic potential of Asparagus dumosus using formaldehyde and CFA-induced arthritic models in rats via modulation of oxidative stress biomarkers and mRNA expression of IL-1b, IL-6, RANKL, OPG, TNF-α and COX-2 - Nimra Nazar; Malik Hassan Mehmood; Rida Siddique; Muhammad Naeem Faisal (Inflammopharmacology, 2025)

Gene editing and GWAS for digital imaging analysis of wheat grain weight, size and shape are inevitable to enhance the yield - Muhammad Jamil; Waseem Ahmad; Muhammad Sanwal; Muhammad Faisal Maqsood (Cereal Research Communications, 2025)

The green supply chain conundrum: exploring the interplay of practices, performance, and technology in shaping SME sustainability in developing country - Ikramuddin Junejo; Jan Muhammad Sohu; Aiza Aziz Qureshi; Saba Shaikh; Faisal Ejaz; Tahir Saeed Jagirani; Md Billal Hossain (Environment, Development and Sustainability, 2025)

Correction to: Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2025)

Ore genesis and critical metal enrichment using deep learning algorithms in Gunga Pb-Zn deposit, Southern Pakistan: Constraints from sphalerite geochemistry and isotopic compositions - Muhammad A. Gul; Huishan Zhang; Yu Yang; Guangli Ren; Chao Sun; Xiaojian Zhao; Tahir Bin Yousuf; Ahmed Shah; Rizwan Sarwar Awan; Mohamed Faisal; Xiaoyong Yang (Journal of Geochemical Exploration, 2025)

Association of microplastics with lead and cadmium in soil: Land-use and temporal trends - Noreen Khalid; Muhammad Aqeel; Shiou Yih Lee; Ujala Ejaz; Ali Noman; Muhammad Faisal Maqsood; Muhammad Kashif Irshad; Mohamed A. El-Sheikh (Journal of Environmental Chemical Engineering, 2025)

Enhanced electrochemical performance of MoP2-based supercapacitor electrodes through doping with transition, post-transition, and rare earth metals - Mudassar Maraj; Mir Rehman Shabbir; Faisal Ali; Muhammad Hamza Naseer; Ali Haider Bhalli; Sarmad Ali; Nian Li; Xiuhong Li; Zhenyang Wang (Fuel, 2025)

Microbial Synthesis of ZnO Nanoparticles: A Green Strategy for Mitigating Wastewater Stress in Wheat (Triticum aestivum) - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Hafiz Muhammad Rizwan; Muhammed Umair Hassan; Muhammad Irfan; Muhammad Adnan; Faisal Mahmood (Water, Air, & Soil Pollution, 2025)

Jasmonic Acid as a Regulator in Plant Stress Tolerance: Mechanisms and Agricultural Implications - Jalil Ahmad; Faisal Hayat; Ummara Khan; Muhammad Ahsan Altaf; Muhammad Ahmad; Muhammad Tahir Akram; Karthishwaran Kandhan; Mohamed S. Sheteiwy; Juan Li; Mohammed Alyafei (Journal of Crop Health, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

Potential beneficial effects of dietary replacement of fish meal with Black soldier fly (Hermetia illucens) larvae meal on growth, general physiology, and microanatomy of Nile tilapia (Oreochromis niloticus) - Waqar Younas; Amina Zuberi; Faisal Ahmad Lodhi; Muhib Zaman; Muhammad Noorullah; Muhammad Ali (Fish Physiology and Biochemistry, 2025)

Evaluation of the shallow hydrothermal system in Jaboi Volcano based on the combination of remote sensing and geophysical measurements - Muhammad Yanis; Muhammad Isa; Nasrullah Zaini; Faisal Abdullah; Muksin Umar; Marwan; Cutti Zahrati; Bondan Galih Dewanto; Riski Ananda; Azman Abdul Ghani (Geosciences Journal, 2025)

Evaluation of entomopathogenic fungi and nematode species for eco-friendly management of fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) - Usama Saleem; Muhammad Asrar; Dilbar Hussain; Faisal Hafeez; Muhammad Sohail Qadir (International Journal of Tropical Insect Science, 2025)

Adaptive divergence in Ostrinia furnacalis: Diet-based fitness specification across wild, domestic and hybrid populations - Aleena Alam; Sohail Abbas; Faisal Hafeez; Muhammad Shakeel; Arzlan Abbas; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Adil Tonğa; Rizhao Chen (Crop Protection, 2025)

Geological and geochemical evolution of the Derhib sulfide-talc deposit in the South Eastern Desert, Egypt: Insights into ore genesis and metasomatic alteration - Mohamed Faisal; Huan Li; Rub'son N'nahano Heritier; Muhammad A. Gul; Farah A. Khedr; Zhekai Zhou; Sobhi M. Ghoneim (Lithos, 2025)

Rapid wall shear stress prediction for aortic aneurysms using deep learning: a fast alternative to CFD - Md. Ahasan Atick Faisal; Onur Mutlu; Sakib Mahmud; Anas Tahir; Muhammad E. H. Chowdhury; Faycal Bensaali; Abdulrahman Alnabti; Mehmet Metin Yavuz; Ayman El-Menyar; Hassan Al-Thani; Huseyin Cagatay Yalcin (Medical & Biological Engineering & Computing, 2025)
Aortic aneurysms pose a significant risk of rupture. Previous research has shown that areas exposed to low wall shear stress (WSS) are more prone to rupture. Therefore, precise WSS determination on the aneurysm is crucial for rupture risk assessment. Computational fluid dynamics (CFD) is a powerful approach for WSS calculations, but they are computationally intensive, hindering time-sensitive clinical decision-making. In this study, we propose a deep learning (DL) surrogate, MultiViewUNet, to rapidly predict time-averaged WSS (TAWSS) distributions on abdominal aortic aneurysms (AAA). Our novel approach employs a domain transformation technique to translate complex aortic geometries into representations compatible with state-of-the-art neural networks. MultiViewUNet was trained on $$\varvec{23}$$ 23 real and $$\varvec{230}$$ 230 synthetic AAA geometries, demonstrating an average normalized mean absolute error (NMAE) of just $$\varvec{0.362%}$$ 0.362 % in WSS prediction. This framework has the potential to streamline hemodynamic analysis in AAA and other clinical scenarios where fast and accurate stress quantification is essential. Graphical abstract

Seismic evaluation and strengthening of an RC building using different retrofit techniques in earthquake-prone region of Pakistan - Obaidullah Khan; Muhammad Faisal Javed; Adeel Zafar; Sanaullah Khan (Innovative Infrastructure Solutions, 2025)

Building a high-resolution seismic impedance model via application of a novel grid conversion technique: implications for gas reservoirs - Tahir Azeem; Wang Yan Chun; Faisal Rehman; Muhammad Toqeer; Aamir Ali (Arabian Journal of Geosciences, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Feather keratin-based hybrid adsorbents: Reproducibility and efficacy in metal removal from synthetic wastewater - Irum Zahara; Muhammad Faisal Irfan; Tariq Siddique; Aman Ullah (Journal of Water Process Engineering, 2025)

Pharmacotherapeutic role of astringin against chromium induced nephrotoxicity via modulating TLR4/MyD88, HMGB1/RAGE and NF-κB pathway: A biochemical and pharmacokinetic approach - Han Hu; Muhammad Faisal Hayat; Syeda Sania Zahara; Ali Akbar; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani; Ahmed Al-Emam (Journal of Trace Elements in Medicine and Biology, 2025)

From bias to accuracy: Transforming satellite precipitation data in arid regions with machine learning and topographical insights - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2025)

Removal of nickel ions from industrial wastewater using tms-EDTA-functionalized Ti3C2Tx: Experimental and statistical physics modeling - Syed Asad Raza Kazmi; Syed Muhammad Husnain; Abdul Rehman Khan; Tariq M. Qureshi; Tarek Lemaoui; Inas M. AlNashef; Hassan A. Arafat; Faisal Shahzad (Journal of Hazardous Materials, 2025)

Sorbitol induces sub-chronic nephrotoxicity via escalating JAK1/STAT3, oxidative stress and inflammation in Sprague Dawley rats - Fuad M. Alzahrani; Aqsa Bibi; Muhammad Faisal Hayat; Khalid J. Alzahrani; Khalaf F. Alsharif; Adnan Ali (Food and Chemical Toxicology, 2025)

Elaidic acid induces testicular oxidative stress, inflammation, Wnt/β-catenin disruption and abnormalities in steroidogenesis, spermatogenesis and histo-architecture in Sprague Dawley rats - Fuad M. Alzahrani; Muhammad Faisal Hayat; Ali Akbar; Syeda Sania Zahara; Meshari A. Alsuwat; Khalid J. Alzahrani; Ahmed Al-Emam (Food and Chemical Toxicology, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Interactive Effects of Biochar Rates and Elevated Temperature on Organic Matter Cycling and Extracellular Enzyme Activity in a Sandy Loam Aridisol - Rummana Basit Mir; Muhammad Sanaullah; Faisal Mahmood; Sabir Hussain; Muhammad Hussnain Siddique; Hayssam M. Ali; Xingliang Xu; Afzal Ahmed; Umme-e-Aiman Fiaz; Tanvir Shahzad (Journal of Soil Science and Plant Nutrition, 2025)

Mitigating the Greenhouse Gases Intensity and Improving Fine Rice Productivity with Coated Urea Fertilizers in Semi-Arid Conditions - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Hafiz Abdul Wahab; Faisal Nadeem; Rikza Awan; Uthman Balgith Algopishi; Mohamed Hashem; Muhammad Umair Hassan (Journal of Soil Science and Plant Nutrition, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Characterization of date palm (Phoenix dactylifera L.) cultivars in Kech, Balochistan-Pakistan: antioxidant properties, phytochemical profiling and mineral composition - Muhammad Waseem; Summar Abbas Naqvi; Muhammad Jafar Jaskani; Faisal Saeed Awan (Genetic Resources and Crop Evolution, 2025)

Exploring the morpho-physiological responses of maize to nickel stress modulated by salicylic acid - Atifa Masood; Sumaira Arooj; Muhammad Shahbaz; Noreen Khalid; Muhammad Sajjad; Muhammad Faisal Maqsood; Sunbal Khalil Chaudhari; Abida Abid; Rafia Zainab; Noor Fatima (Cereal Research Communications, 2025)

Relative change in accommodation space and sedimentation rates of Jurassic to Middle Eocene sedimentary facies in the NW Himalaya, Pakistan - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj; Shaukat Ali; Faisal Shah; Syed Kamran Ali (Carbonates and Evaporites, 2025)

Investigating the Role of Gibberellic Acid in Fruit Drop Mitigation and Fruit Quality Improvement in Date Palm Cultivars - Hammad Hussain; Yue Yu; Abdul Haseeb Ahmed; Faisal Hayat; Muhammad Awais; Abdullah Ma’Arij; Guo Wei; Rashad Qadri (Applied Fruit Science, 2025)

Digital twins: cornerstone to circular economy and sustainability goals - Zain Anwar Ali; Mahreen Zain; Raza Hasan; Muhammad Salman Pathan; Hussain AlSalman; Faisal Abdulaziz Almisned (Environment, Development and Sustainability, 2025)
Accurate information is a prerequisite for circulation and greater longevity of materials and products, enabling the economically and environmentally successful transition of circular economy (CE) in the aspiration towards sustainable development. However, a lack of appropriate digital tools is noticed in supplying relevant information and supporting recyclability, reusability, and reducibility processes. This study focuses on a building block of evolving technologies anointed the digital twin (DT). It aims to conceptualize DT as a cornerstone for the CE paradigm, positively influencing sustainability. It also endeavors to scrutinize remarkable implementations of DT-driven CE, accomplishing sustainable development goals (SDGs) in Ireland. An iterative methodology based on four steps is adopted to review an explosion of relevant, recent literature published in 2019–2024 and multiple case studies of Irish construction and manufacturing sectors. By analyzing the literature, this study discovers the evolution and taxonomy of DT, other technologies essential for its deployment, its proactive role in implementing CE and SDGs, and some challenges. Key findings of case studies reveal the current trajectory of employing DT with other digital products, upholding the CE practices within the bounds of the SDGs in Irish companies. In conclusion, DT is a conceivable means for advancing CE solutions and attaining SDGs towards social, economic, and environmental sustainability. The implications of this study are both theoretically and practically significant, encouraging industrialists and academia to adopt DT. It will help scholars gain a thorough understanding and guide industrialists to downsize their carbon footprint and waste, accomplishing SDGs. It will inspire managers with DT-driven information for decision-making and facilitate government and policymakers to collaborate in designing essential policies. Graphical Abstract

Revisiting the composite drought index for improving drought monitoring - Muhammad Abrar Faiz; Liangliang Zhang; Dong Liu; Ning Ma; Mo Li; Zhaoqiang Zhou; Faisal Baig; Tianxiao Li; Song Cui (Journal of Hydrology, 2025)

Machine learning-driven classification of Pb Zn ore deposits using pyrite trace elements and isotopic signatures: A case study of the Gunga deposit - Muhammad Amar Gul; Huishan Zhang; Yanguang Li; Xiaoyong Yang; Chao Sun; Xiaojian Zhao; Guangli Ren; Asia Kanwal; Muhammad Hafeez; Yu Yang; Rizwan Sarwar Awan; Mohamed Faisal (Journal of Geochemical Exploration, 2025)

Experimental and first-principles analyses of oxidative defect removal in eco-friendly InP quantum dot synthesis via in situ HF etching - Awais Ali; Faisal Rehman; Tridip Das; Muhammad Imran; Junhyeok Park; Seongkeun Oh; Hanseok Seo; Young Kyun Choi; William A Goddard; Soong Ju Oh (Chemical Engineering Journal, 2025)

Correction: Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

Integrated geophysical and hydrogeological techniques for environmental monitoring and assessment: a case study for waste disposal site, Jeddah Saudi, Arabia - Faisal Rehman; Helmy S. O. Abuelnaga; Hussein M. Harbi; Tahir Azeem; Jamil Siddique; Omar Riaz; Muhammad Fahad Ullah; Faisal Rehman (Arabian Journal of Geosciences, 2025)

Biomonitoring and phytoremediation potential of Conocarpus erectus (Buttonwood) for mitigating air pollution from highway traffic - Akkasha Azam; Ummar Iqbal; Zartasha Usman; Muhammad Sharif; Muhammad Faisal Gul; Nargis Naz; Ifrah Nawaz; Farooq Ahmad (Chemosphere, 2025)

Effects of electromagnetic radiation from offshore wind power on the physiology and behavior of two marine fishes - Peng Xu; Bole Wang; Zhenghao Wang; Renkang Jin; Manzoor Ahmad; Yueyong Shang; Menghong Hu; Fangping Chen; Muhammad Faisal Khalil; Wei Huang; Youji Wang (Marine Pollution Bulletin, 2025)

Palliative potential of genistein to counteract endosulfan instigated colon toxicity via regulating TLR4/MyD88, JAK1/STAT3 and NF-κB pathway: A biochemical and histological approach - Khalid J. Alzahrani; Mahmoud El Safadi; Khalaf F. Alsharif; Fuad M. Alzahrani; Muhammad Faisal Hayat (Tissue and Cell, 2025)

Afzelechin alleviates deltamethrin induced hepatic dysfunction via regulating TLR4/MyD88, HMGB1/RAGE and NF-κB pathway - Fuad M. Alzahrani; Khalid J. Alzahrani; Khalaf F. Alsharif; Muhammad Faisal Hayat; Ahmed Al-Emam (Toxicology and Applied Pharmacology, 2025)

g-C3N4-modulated CdS-V2O5/g-C3N4 nanosheets as efficient alkaline OER and HER electrocatalyst for water-splitting - Tauseef Munawar; Ambreen Bashir; Faisal Iqbal; Muhammad Rafaqat; Changqing Guo; Mohammad Zhiani; Chenglin Zhao; Yongfeng Tong; Shoukat Alim Khan; Muammer Koc; Chang-Feng Yan (Fuel, 2025)

Evaluation of antibody titer and associated risk factors of goat pox vaccine against lumpy skin disease in crossbred buffaloes - Adili Abulaiti; Zahid Naseer; Zulfiqar Ahmed; Shijun Tian; Wenju Liu; Muhammad Shoaib; Asghar Khan; Mohamed Abdelrahman; Faisal Ayub Kiani; Abid Hussain; Aftab Shaukat; Umair Riaz; et al. (Veterinary Research Communications, 2025)

Tissue-specific inhibition of brassinosteroids regulates panicle branching and grain yield in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Xiaoyu Guo; Daowen Wang; Guang Qi (Science China Life Sciences, 2025)

Self-nanoemulsifying drug delivery system for nebulization: fabrication and evaluation for systemic delivery of atorvastatin - Muhammad Danish Saeed; Kifayat Ullah Shah; Muhammad Fahad; Shefaat Ullah Shah; Syed Faisal Badshah; Hassan Shah; Irfan Anjum; Gamal A. Shazly; Mohammed Bourhia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nanoparticle-Mediated Phytohormone Interplay: Advancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Fozia Farhat; Saher Nawaz; Muhammad Ahmad (Journal of Crop Health, 2025)

Blood, feathers, and eggs as bioindicators of selenium sources and their impact on DNA damage in Japanese quails (Coturnix japonica) - Aimen Khalid; Sania Satti; Anqash Ayyub; Faisal Nawab; Muhammad Tahir; Shabana Naz; Mikhlid H. Almutairi; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Demilade Israel Ibiwoye (Research in Veterinary Science, 2025)

Soil amendment with Dryopteris nigropaleacea enhances natural control of Fusarium wilt by modulating morphological, biochemical, and physiological traits of tomato plants - Faisal Iqbal Jafri; Muhammad Akbar; Muhammad Zia ur Rehman; Mohsin Khurshid (Physiological and Molecular Plant Pathology, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

Unveiling the future: Breakthroughs and innovations in MXene-based electrochemical sensors - Muhammad Khan; Xiaohui Sun; Faisal Attique; Muhammad Tahir Saleh; Naveed Ahmad; Kainat Atiq; Muhammad Shafi; Inas A. Ahmed; Imad Barsoum; Muhammad Shahbaz Rafique; Azeem Ullah; Amjad Hussain; et al. (Chemical Engineering Journal, 2025)

Effect of different likelihood measures on parameter conditioning and model uncertainty - Faisal Baig; Mehmet Cuneyd Demirel; Muhammad Yousaf Raza Taseer; Assaad Kassem; Mohsen Sherif (Stochastic Environmental Research and Risk Assessment, 2025)

Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

Theabrownin: a dietary nutraceutical with diverse anticancer mechanisms - Muhammad Faisal Maqbool; Sameena Gul; Muhammad Ishaq; Amara Maryam; Muhammad Khan; Hafiz Abdullah Shakir; Muhammad Irfan; Yongming Li; Tonghui Ma (Natural Product Research, 2025)

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Effects of functionalized nanoplastics on oxidative stress in the mussel Mytilus coruscus - Peiwen Yang; Yueyong Shang; Bin Qu; Jinping Zhang; Muhammad Faisal Khalil; Menghong Hu; Youji Wang (Marine Pollution Bulletin, 2025)

Do structural and functional traits modulation determine the ecological fate of castor bean (Ricinus communis L.) under variable pedospheric and atmospheric conditions? - Ummar Iqbal; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (South African Journal of Botany, 2025)

Enhanced electrochemical performance of ZrTe-Mn2O3 nanocomposite electrocatalyst for HER and OER in alkaline medium - Tauseef Munawar; Saman Fatima; Faisal Iqbal; Ambreen Bashir; Muhammad Rafaqat; Zhiming Tu; Lisha Shen; Shoukat Alim Khan; Muammer Koc; Chang-Feng Yan (Fuel, 2025)

Amine-functionalized organically modified silica for the effective adsorption of Chlorpyrifos and Triazophos Residues from Orange juice - Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Hina Raza; Ayesha Javid; Zeeshan Ali; Muhammad Imran Khan; Faisal K. Algethami; Najla AlMasoud; Taghrid S. Alomar (Food Chemistry, 2025)

Buckling behavior of orthotropic thin plates using analytical and machine learning methods - Salamat Ullah; Jincheng Zhang; Hu Bo; Jinghui Zhang; Muhammad Faisal Javed; Weiqiu Chen (Engineering Structures, 2025)

Intermittent Fasting and Probiotics: Synergistic Modulation of Gut Health for Therapeutic Advantages - Amna Shehbaz; Muhammad Afzaal; Noor Akram; Farhan Saeed; Warda Khan; Faiyaz Ahmed; Aftab Ahmed; Aasma Asghar; Zargham Faisal (Probiotics and Antimicrobial Proteins, 2025)

Unraveling insect feeding patterns and their ecological impacts on plant defense mechanisms - Arzlan Abbas; Muhammad Zulqar Nain Dara; Farman Ullah; Babu Saddam; Sohail Abbas; Aleena Alam; Mobeen Babar; Faisal Hafeez; Muhammad Dildar Gogi; Hamed A. Ghramh; Khalid Ali Khan; Yasir Niaz; et al. (Journal of Plant Diseases and Protection, 2025)

Human Brucellosis in the Rural and Urban Population of Pakistan: Seroprevalence, Risk Factors, and Clinical Manifestations - Faisal Abbas; Shahzad Ali; Ali Muhammad; Asima Azam; Amira A. Moawad; Mohammad Ejaz; Anam Iftikhar; Maryam Dadar (Current Microbiology, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Investigating Bemisia tabaci (Hemiptera: Aleyrodidae) resistance mechanisms: a comprehensive analysis of variable responses to selective insecticides - Dilbar Hussain; Muhammad Saleem; Muhammad Sohail Qadir; Kanwal Hanif; Faisal Hafeez; Usama Saleem; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal; Muhammad Zubair (International Journal of Tropical Insect Science, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

Impact of biogenic zinc oxide nanoparticles on physiological and biochemical attributes of pea (Pisum sativum L.) under drought stress - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Muhammad Iqbal; Faisal Mahmood; Muhammad Umair Hassan (Physiology and Molecular Biology of Plants, 2025)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

Pharmacotherapeutic potential of bilobetin to combat chromium induced hepatotoxicity via regulating TLR-4, Nrf-2/Keap-1, JAK1/STAT3 and NF-κB pathway: A pharmacokinetic and molecular dynamic approach - Mahmoud El Safadi; Muhammad Faisal Hayat; Ali Akbar; Abdullah Nisar; Fuad M. Alzahrani; Khalid J. Alzahrani (Journal of Trace Elements in Medicine and Biology, 2024)

Nutraceutical tablets: Manufacturing processes, quality assurance, and effects on human health - Muhammad Faisal Manzoor; Sakhawat Riaz; Deepak Kumar Verma; Muhammad Waseem; Gulden Goksen; Anwar Ali; Xin-An Zeng (Food Research International, 2024)

Soy protein-polyphenols conjugates interaction mechanism, characterization, techno-functional and biological properties: An updated review - Muhammad Faisal Manzoor; Xin-An Zeng; Muhammad Waseem; Rabia Siddique; Muhammad Rizwan Javed; Deepak Kumar Verma; Murtaza Ali (Food Chemistry, 2024)

Exploring the role of the microbiome of the H. illucens (black soldier fly) for microbial synergy in optimizing black soldier fly rearing and subsequent applications - Muhammad Salam; Viviana Bolletta; Ying Meng; Wael Yakti; Valentina Grossule; Dezhi Shi; Faisal Hayat (Environmental Pollution, 2024)

Salt Stress in Wheat: Effects, Tolerance Mechanisms, and Management - Muhammad Farooq; Noreen Zahra; Aman Ullah; Faisal Nadeem; Abdul Rehman; Riti Kapoor; Mawra S. Al-Hinani; Kadambot H.M. Siddique (Journal of Soil Science and Plant Nutrition, 2024)

Enhancement of Antioxidants’ Enzymatic Activity in the Wheat Crop by Shewanela sp. Mediated Zinc Oxide Nanoparticles Against Heavy Metals Contaminated Wastewater - Irfan Haidri; Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Usman Shafqat; Sadia Mustafa; Faisal Mahmood (Journal of Soil Science and Plant Nutrition, 2024)

Plant Biostimulants: Mechanisms and Applications for Enhancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Kanza Asif; Humaira Ashraf; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Rehana Sardar; Fasih Ullah Haider (Journal of Soil Science and Plant Nutrition, 2024)

Removal of chlorpyrifos from aqueous medium using Ca-CuO@clay nanoflakes coated with deep eutectic solvent - Abdullah Zia; Umer Younas; Zahid Ali; Rabia Nazir; Faisal Ali; Aemin Irfan; Muhammad Pervaiz (Environmental Monitoring and Assessment, 2024)

Hypoxia stress: plant’s sensing, responses, and tolerance mechanisms - Farwa Basit; Muhammad Khalid; Ali El-Keblawy; Mohamed S. Sheteiwy; Saad Sulieman; Izabela Josko; Faisal Zulfiqar (Environmental Science and Pollution Research, 2024)

Copper stress in rice: Perception, signaling, bioremediation and future prospects - Md Mahfuzur Rob; Delara Akhter; Tariqul Islam; Debu Kumar Bhattacharjya; Muhammad Saad Shoaib Khan; Faisal Islam; Jian Chen (Journal of Plant Physiology, 2024)

Optimizing plastic waste inclusion in paver blocks: Balancing performance, environmental impact, and cost through LCA and economic analysis - Usama Asif; Muhammad Faisal Javed (Journal of Cleaner Production, 2024)

Land subsidence and groundwater storage change assessment using InSAR and GRACE in the arid environment of Saudi Arabia - Esubalew Adem; Roman Shults; Muhammad Ukasha; Amro Elfeki; Faisal Alqahtani; Mohamed Elhag (Natural Hazards, 2024)

In silico genome-wide analysis of the growth-regulating factor gene family and their expression profiling in Vitis vinifera under biotic stress - Nimra Nazir; Azhar Iqbal; Hadia Hussain; Faisal Ali; Khalid S. Almaary; Most. Nazmin Aktar; Muhammad Sajid; Mohammed Bourhia; Ahmad Mohammad Salamatullah (Cell Biochemistry and Biophysics, 2024)

Bio-based microplastic polylactic acid exerts the similar toxic effects to traditional petroleum-based microplastic polystyrene in mussels - Zhen Zhong; Wenrui Shang; Peiwen Yang; Shixiu Wang; Liming Chen; Zhaowen Chen; Li’ang Li; Muhammad Faisal Khalil; Menghong Hu; Xiangrong Xu; Youji Wang (Science of The Total Environment, 2024)

Surviving the desert's grasp: Decipherment phreatophyte Tamarix aphylla (L.) Karst. Adaptive strategies for arid resilience - Ummar Iqbal; Ali Daad; Ahmad Ali; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (Plant Science, 2024)

Bovine colostrum: Therapeutic potential and clinical evidence - Talha Shireen Khan; Noor Akram; Zargham Faisal; Farhan Saeed; Amara Rasheed; Faiyaz Ahmed; Muhammad Afzaal (International Dairy Journal, 2024)

Fine-tuning plant valuable secondary metabolite biosynthesis via small RNA manipulation: strategies and potential - Nur Irdina Izzatie Mohd Zahid; Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Ismanizan Ismail; Muhamad Hafiz Che-Othman (Planta, 2024)

Gingerol nanoparticles attenuate complete Freund adjuvant-induced arthritis in rats via targeting the RANKL/OPG signaling pathway - Rida Siddique; Faqir Muhammad; Muhammad Naeem Faisal; Bushra Akhtar; Ammara Saleem; Shaneel Kousar; Ali Sharif; Muhammad Saeed; Safwan Muhammad (Inflammopharmacology, 2024)

Investigation of drying shrinkage response in fibrillated microfiber reinforced preplaced concrete: experimental analysis and prediction models - Muhammad Saqib; Muhammad Faisal Javed; M. Ijaz Khan (Innovative Infrastructure Solutions, 2024)

Optimized prediction modeling of micropollutant removal efficiency in forward osmosis membrane systems using explainable machine learning algorithms - Ali Aldrees; Muhammad Faisal Javed; Majid Khan; Bilal Siddiq (Journal of Water Process Engineering, 2024)

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Consumer pesticide concerns and the choice of fruit and vegetable markets in five low- and middle-income countries - Justice A. Tambo; Monica K. Kansiime; Jayanthi R. Alaganthiran; Muhammad Danish; Solomon A. Duah; Shah Faisal; Makaiko G. Khonje; Fredrick Mbugua; Ganeshamoorthy Rajendran (Global Food Security, 2024)

Resilient mechanism of strigolactone (GR24) in regulating morphological and biochemical status of maize under salt stress - Iqra Iftikhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Shamsa Rana; Fozia Farhat; Hira Farooq; Kamran Ahmad; Muhammad Jamil; Fasih Ullah Haider; Saltanat Aghayeva (Biocatalysis and Agricultural Biotechnology, 2024)

Nano-Selenium: A Green Promising Approach against Abiotic Stresses in Plants - Mariam Fatima; Asia Maqbool; Rehana Sardar; Muhammad Faisal Maqsood; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Recent innovations and emerging technological advances used to improve quality and process of plant-based milk analogs - Taha Mehany; Shahida Anusha Siddiqui; Babatunde Olawoye; Oyekemi Olabisi Popoola; Abdo Hassoun; Muhammad Faisal Manzoor; Sneh Punia Bangar (Critical Reviews in Food Science and Nutrition, 2024)

Insights in to iron-based nanoparticles (hematite and magnetite) improving the maize growth (Zea mays L.) and iron nutrition with low environmental impacts - Nauman Yousaf; Muhammad Fahad Sardar; Muhammad Ishfaq; Baogang Yu; Yanting Zhong; Faisal Zaman; Fusuo Zhang; Chunqin Zou (Chemosphere, 2024)

Integrative approach to the biochemical, and toxicological fingerprinting of Polygonum glabrum.: A computational and experimental synergy for a medicinal food plant - Sumera Hanif; Muhammad Faisal Nadeem; Haji M. Shoaib Khan; Muhammad Naeem; Anjum Khursheed; Abdulwahab Alamri; Mhdia Elhadi Osman; Adel Alghamdi; Nasrin E. Khalifa; Marcello Locatelli; Syafiq Asnawi Zainal Abidin (Food Bioscience, 2024)

Environmentally responsive changes in mucus indicators and microbiota of Chinese sturgeon Acipenser sinensis - Shen Jin; Jiehao Liu; Yueping Zheng; Jianan Xu; Houyong Fan; Muhammad Faisal Khalil; Youji Wang; Menghong Hu (Fish & Shellfish Immunology, 2024)

Phytoremediation of Arsenic (As) in rice plants, mediated by strain IU31 through antioxidant responses and phytohormones synthesis - Ihsan Ullah; Yasir Anwar; Muhammad Faisal Siddiqui; Nadiah Alsulami; Raza Ullah (Environmental Pollution, 2024)

Chemical analogue based drug design for cancer treatment targeting PI3K: integrating machine learning and molecular modeling - Mohammed A. Bazuhair; Anwar A. Alghamdi; Othman Baothman; Muhammad Afzal; Sami I. Alzarea; Faisal Imam; Ehssan Moglad; Hisham N. Altayb (Molecular Diversity, 2024)

Satellite-based rainwater harvesting sites assessment for Dera Ghazi Khan, Punjab, Pakistan - Samman Aziz; Muhammad Y. S. Dasti; Mashal Abrar; Faisal Mumtaz; Aqil Tariq (Environmental Science and Pollution Research, 2024)

Synergistic effect of biochar with gypsum, lime, and farm manure on the growth and tolerance in rice plants under different salt-affected soils - Yousef Alhaj Hamoud; Talha Saleem; Muhammad Zia-ur-Rehman; Hiba Shaghaleh; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Faisal Al-Sarraj; Nadiyah M. Alabdallah (Chemosphere, 2024)

Physicochemical properties and performance of non-woody derived biochars for the sustainable removal of aquatic pollutants: A systematic review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Rashid Iqbal; Faisal Zulfiqar; Akash Tariq; Allah Ditta (Chemosphere, 2024)

Ameliorative potential of eriocitrin against cadmium instigated hepatotoxicity in rats via regulating Nrf2/keap1 pathway - Muhammad Faisal Hayat; Muhammad Zohaib; Muhammad Umar Ijaz; Moazama Batool; Asma Ashraf; Bader O. Almutairi; Usman Atique (Journal of Trace Elements in Medicine and Biology, 2024)

Strengthening oil pollution monitoring system in aquatic environment through development of IoT-based Oil-Water Separator Device - Faisal Budiman; Abrar Ismardi; Tri Hardinah; Rayi Muhammad; Nurwijayadi; Aris Hartaman; Agus Nurhidayat; Iman H.S. Sasto; Ignasius D.A. Sutapa (Ecohydrology & Hydrobiology, 2024)

Development and validation of an indirect ELISA for the serodiagnosis of contagious caprine pleuropneumonia in goats - Hayatullah Khan; Farhan Anwar Khan; Umer Sadique; Ijaz Ahmad; Muhammad Saeed; Faisal Ahmad; Faiz Ur Rehman; Hanif Ur Rahman (Small Ruminant Research, 2024)

Impact of sustainable emerging cold plasma technology on the optical properties of foods - Murtaza Ali; Muhammad Faisal Manzoor; Xin-An Zeng; Afeera Abida; Ume Roobab (Food Bioscience, 2024)

Emerging high intensity ultrasound for soymilk in boosting bioactivity, amino acids release, reducing anti-nutritional factors and allergenicity - Muhammad Hussain; Hao Zhong; Kifayat Hussain; Muhammad Faisal Manzoor; Abdul Qayum; Xiaofeng Liu; Jie Xu; Abid Hussain; Hafiz Muhammad Ahsan; Rongfa Guan (Food Bioscience, 2024)

RETRACTED: Boosted charge separation via Ce2S3 over dual Z-scheme ZnO–Ce2S3–MnO2 core double-shell nanocomposite for the degradation of diverse dye pollutants - Tauseef Munawar; Taghrid S. Alomar; Chang-Feng Yan; Saman Fatima; Faisal Mukhtar; Muhammad Shahid Nadeem; Najla AlMasoud; Shoukat Alim Khan; Muammer Koc; Yahya Zakaria; Faisal Iqbal (Environmental Research, 2024)

Evolution and Trends of Water Scarcity Indicators: Unveiling Gaps, Challenges, and Collaborative Opportunities - Zafar Hussain; Zongmin Wang; Haibo Yang; Muhammad Arfan; Wusen Wang; Muhammad Faisal; Muhammad Imran Azam; Muhammad Usman (Water Conservation Science and Engineering, 2024)

Repurposing FDA approved drugs against monkeypox virus DNA dependent RNA polymerase: virtual screening, normal mode analysis and molecular dynamics simulation studies - Ahmad Abdul Salam Khan; Muhammad Abrar Yousaf; Jahanzaib Azhar; Muhammad Faisal Maqbool; Ruqia Bibi (VirusDisease, 2024)

Enhancing Plant Stress Resilience with Osmolytes and Nanoparticles - Yumna Rasheed; Faizan Khalid; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Nargis Naz; Muhammad Shahbaz; Usman Zulfiqar; Qasim Ali; Shamsa Rana (Journal of Soil Science and Plant Nutrition, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Examining drinking water quality: analysis of physico-chemical properties and bacterial contamination with health implications for Shangla district, Khyber Pakhtunkhwa, Pakistan - Muhammad Salam; Dong Bo; Fakhri Alam; Islam Uddin; Md. Nuralam Hossain; Faisal Hayat; Waheed Ullah (Environmental Geochemistry and Health, 2024)

Zinc oxide application alleviates arsenic-mediated oxidative stress via physio-biochemical mechanism in rice - Sanaullah Jalil; Muhammad Mudassir Nazir; Mohamed A. Eweda; Faisal Zulfiqar; Temoor Ahmed; Muhammad Noman; Muhammad A. U. Asad; Kadambot H. M. Siddique; Xiaoli Jin (Environmental Science and Pollution Research, 2024)

Depositional cyclicity of lower Cambrian strata in the NW Himalayas: Regional sequence stratigraphy of the Indian passive margin - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj (Marine and Petroleum Geology, 2024)

Downscaled GRACE/GRACE-FO observations for spatial and temporal monitoring of groundwater storage variations at the local scale using machine learning - Shoaib Ali; Jiangjun Ran; Behnam Khorrami; Haotian Wu; Aqil Tariq; Muhammad Jehanzaib; Muhammad Mohsin Khan; Muhammad Faisal (Groundwater for Sustainable Development, 2024)

Temperature-dependent transformation of microbial community: A systematic approach to analyzing functional microbes and biogas production - Ali Bahadur; Lu Zhang; Wei Guo; Wasim Sajjad; Nikhat Ilahi; Abhishek Banerjee; Shah Faisal; Muhammad Usman; Tuo Chen; Wei Zhang (Environmental Research, 2024)

Multi-aspect analysis of an innovative environmentally friendly process integrated into a gas turbine power plant using a multi-heat recovery approach - Shah Faisal; B. Nageswara Rao; Mohamad Abou Houran; Manoj Kumar Agrawal; Mohamed Ayadi; Jong Boon Ooi; Nehad Ali Shah; Taseer Muhammad; Tiancheng Ji (Desalination, 2024)

Impact of dichromatic lighted incubation on hatching result and post-hatch performance of broiler chickens - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Saima (Tropical Animal Health and Production, 2024)

Melatonin alleviates cadmium phytotoxicity through regulation of growth, photosynthesis, and antioxidant potential in two pepper genotypes - Muhammad Saqib; Umbreen Shahzad; Zakia Abid; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Waleed Amjad Khan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (Acta Physiologiae Plantarum, 2024)

Efficacy of different blood meals for the mass rearing of Aedes aegypti (Diptera: Culicidae) population - Shahid Majeed; Muhammad Sufyan; Asim Abbasi; Muhammad Binyameen; Ramish Saleem; Wafa A. H. Alkherb; Shahla Faisal; Jamil Ijaz; Hira Hameed (International Journal of Tropical Insect Science, 2024)

RETRACTED: Borage leaf extract improves the vase life of cut gladiolus flowers by delaying the senescence process and reducing water stress - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Anastasios Darras; Mohamed S. Sheteiwy; Baber Ali; Muhammad Ahsan Altaf; Walid Soufan; Ayman El Sabagh (Postharvest Biology and Technology, 2024)

How accurate are the machine learning models in improving monthly rainfall prediction in hyper arid environment? - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Preharvest Application of Hydrogen Sulfide and Nitric Oxide Improves Floral Traits and Postharvest Performance of Cut Gladiolus Inflorescences - Faisal Zulfiqar; Anam Moosa; Anastasios Darras; Muhammad Nafees; Muhammad Ashraf; Ibrahim Al-Ashkar; Ayman El Sabagh; John T. Hancock (Journal of Plant Growth Regulation, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Genetic biofortification: advancing crop nutrition to tackle hidden hunger - Usman Zulfiqar; Amman Khokhar; Muhammad Faisal Maqsood; Muhammad Shahbaz; Nargis Naz; Maheen Sara; Sana Maqsood; Sajila Sahar; Saddam Hussain; Muhammad Ahmad (Functional & Integrative Genomics, 2024)

Retraction Note: The role of monetary and fiscal policies in determining environmental pollution: Revisiting the N-shaped EKC hypothesis for China - Tang Zhengxia; Mohammad Haseeb; Muhammad Usman; Mohd Shuaib; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2024)

Temperature drives microbial communities in anaerobic digestion during biogas production from food waste - Tuo Chen; Lu Zhang; Wei Guo; Wei Zhang; Wasim Sajjad; Nikhat Ilahi; Muhammad Usman; Shah Faisal; Ali Bahadur (Environmental Science and Pollution Research, 2024)

Harnessing soil carbon sequestration to address climate change challenges in agriculture - Muhammad Junaid Nazir; Guanlin Li; Muhammad Mudassir Nazir; Faisal Zulfiqar; Kadambot H.M. Siddique; Babar Iqbal; Daolin Du (Soil and Tillage Research, 2024)

Co-application of biochar and salt tolerant PGPR to improve soil quality and wheat production in a naturally saline soil - Laraib Malik; Muhammad Sanaullah; Faisal Mahmood; Sabir Hussain; Tanvir Shahzad (Rhizosphere, 2024)

Innovative modification process of a natural gas power plant using self-sufficient waste heat recovery and flue gas utilization for a CCHP-methanol generation application: A comprehensive multi-variable feasibility study - Shah Faisal; Amir Abbas; Aboulbaba Eladeb; Manoj Kumar Agrawal; Taseer Muhammad; Mohamed Ayadi; Kaouther Ghachem; Lioua Kolsi; Min Wang; Ahmad Mustafa (Process Safety and Environmental Protection, 2024)

Natural deep eutectic solvent: A promising eco-friendly food bio-inspired antifreezing - Xue Li; Jia-Ying Li; Muhammad Faisal Manzoor; Qiu-Ya Lin; Jia-ling Shen; Lan Liao; Xin-An Zeng (Food Chemistry, 2024)

Vegetable Plant Canopy Inhibits Soil Urease Activity and Reduces NH3 Losses Under p-Phenylenediamine (PPD)-Coated Urea Application - Sarah Shakeel; Rashid Mahmood; Ammara Fatima; Faisal Nadeem; Sajid Ali; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Tracking the Feeding Mechanism of Sap-Sucking Insect-Pests Through Electropenetrography (EPG) - Usama Bin Tayyab; Muhammad Jalal Arif; Muhammad Dildar Gogi; Shamim Akhtar; Muhammad Jawad Abdullah; Faisal Ali (Journal of Insect Behavior, 2024)

Bo-derived waste neem to enriching reinforced hybrid composite for environmental remediation - Gnanasambandam Anbuchezhiyan; Nabisab Mujawar Mubarak; Muhammad Tahir Hussain Siddiqui; Guilherme Malafaia; Faisal Abnisa (Chemosphere, 2024)

The nexus between resource depletion, price fluctuations, and sustainable development in expenditure on resources - Tianyang Wang; Menggang Li; Muhammad Faisal Rasheed (Resources Policy, 2024)

Assessing the impact of RCP4.5 and RCP8.5 scenarios on landslide susceptibility mapping using support vector machine: A case study of Penang Island, Malaysia - Mohamed Khatif Tawaf Mohamed Yusof; Ahmad Safuan A Rashid; Mohd Faisal Abdul Khanan; Muhammad Zulkarnain Abdul Rahman; Wardatun Ahmar Abdul Manan; Roohollah Kalatehjari; Ali Dehghanbanadaki (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Nanoparticle elicitation: A promising strategy to modulate the production of bioactive compounds in hairy roots - Kamogelo M. Mmereke; Srividhya Venkataraman; Bertha Nametso Moiketsi; Muhammad Rehan Khan; Sayyeda Hira Hassan; Gaolathe Rantong; Kabo Masisi; Tebogo E. Kwape; Goabaone Gaobotse; Faisal Zulfiqar; Surender Kumar Sharma; Sonia Malik; et al. (Food Research International, 2024)

Sustainable humidity control in the built environment: Recent research and technological advancements in thermal driven dehumidification systems - Muhammad Usman Saeed Akhtar; Sulaiman O. Fadlallah; Muhammad Imran Khan; Faisal Asfand; Sami G. Al-Ghamdi; Rakesh Mishra (Energy and Buildings, 2024)

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

RETRACTED ARTICLE: Assessment of antiarthritic potential of Asparagus dumosus using formaldehyde and CFA-induced arthritic models in rats via modulation of oxidative stress biomarkers and mRNA expression of IL-1b, IL-6, RANKL, OPG, TNF-α and COX-2 - Nimra Nazar; Malik Hassan Mehmood; Rida Siddique; Muhammad Naeem Faisal (Inflammopharmacology, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Melatonin supplementation alleviates drought stress in peach (Prunus persica) seedlings by improving photosynthesis, root morphological traits, and antioxidant defense system - Shahid Iqbal; Faisal Hayat; Mujahid Hussain; Naveed Mushtaq; Muneer Rehman; Alaiha Asif; Ummara Khan; Muhammad Adnan Shahid (Acta Physiologiae Plantarum, 2024)

Fucoidan-based nanomaterial and its multifunctional role for pharmaceutical and biomedical applications - Muhammad Waheed Iqbal; Tahreem Riaz; Shahid Mahmood; Muhammad Bilal; Muhammad Faisal Manzoor; Sarmad Ahmad Qamar; Xianghui Qi (Critical Reviews in Food Science and Nutrition, 2024)

Corrigendum to “Zinc oxide nanoparticles mitigated the arsenic induced oxidative stress through modulation of physio-biochemical aspects and nutritional ions homeostasis in rice (Oryza sativa L.)” [Chemosphere 338 October (2023) 139566] - Sanaullah Jalil; Suliman M.S. Alghanem; Arwa Abdulkreem AL-Huqail; Muhammad Mudassir Nazir; Faisal Zulfiqar; Temoor Ahmed; Sharafat Ali; Amany H.A. Abeed; Kadambot H.M. Siddique; Xiaoli Jin (Chemosphere, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

Assessment of future prediction of urban growth and climate change in district Multan, Pakistan using CA-Markov method - Sajjad Hussain; Muhammad Mubeen; Wajid Nasim; Faisal Mumtaz; Hazem Ghassan Abdo; Raoof Mostafazadeh; Shah Fahad (Urban Climate, 2024)

Global insights into micro-macro mechanisms and environmental implications of limestone calcined clay cement (LC3) for sustainable construction applications - Nauman Ijaz; Wei-Min Ye; Zia ur Rehman; Zain Ijaz; Muhammad Faisal Junaid (Science of The Total Environment, 2024)

Amentoflavone mediated hepatoprotection to counteract paraquat instigated hepatotoxicity via modulating Nrf2/keap1 pathway: A biochemical, inflammatory, apoptotic and histopathological study - Muhammad Umar Ijaz; Naila Ghafoor; Muhammad Faisal Hayat; Bader O. Almutairi; Usman Atique (Pesticide Biochemistry and Physiology, 2024)

Heavy metal(loid)s contamination and ecotoxicological hazards in coal, dust, and soil adjacent to coal mining operations, Northwest Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Journal of Geochemical Exploration, 2024)

Remediation of Cd-polluted soil, improving Brassica napus L. growth and soil health with Hardystonite synthesized with zeolite, limestone, and green Zinc oxide nanoparticles - Fakhir Hannan; Muhamamd Iqbal; Faisal Islam; Muhammamd A. Farooq; Muhammad Bilal Shakoor; Ahsan Ayyaz; Muhammad Saad Shoaib Khan; Juanjuan Li; Qian Huang; Weijun Zhou (Journal of Cleaner Production, 2024)

Scalable synthesis of MOF-derived Nd2O3@C and V2O5@C nanohybrid: Efficient electrocatalyst for OER in alkaline medium - Tauseef Munawar; Ambreen Bashir; Muhammad Shahid Nadeem; Faisal Mukhtar; Sumaira Manzoor; Muhammad Naeem Ashiq; Shoukat Alim Khan; Muammer Koc; Faisal Iqbal (Fuel, 2024)

Unraveling the mechanisms of cadmium toxicity in horticultural plants: Implications for plant health - Muhammad Ahsan Altaf; Safina Naz; Ravinder Kumar; Hasan Sardar; Muhammad Azher Nawaz; Awadhesh Kumar; Priyanka Lal; Riaz Ahmad; Faisal Hayat; Muneeb Ahmad Wani; Rahul Kumar Tiwari; Milan Kumar Lal (South African Journal of Botany, 2023)

Preharvest melatonin application mitigates arsenic-induced oxidative stress and improves vase life of tuberose (Polianthes tuberosa L.) cut flowers - Faisal Zulfiqar; Anam Moosa; Hayssam M. Ali; Antonio Ferrante; Muhammad Mudassir Nazir; Abdullah Makhzoum; Tarek M.A. Soliman (South African Journal of Botany, 2023)

Current understanding of boosting power of salicylic acid for abiotic stress tolerance in horticultural crops - Muhammad Ahsan Altaf; Rabia Shahid; Priyanka Lal; Riaz Ahmad; Faisal Zulfiqar; Awadhesh Kumar; Faisal Hayat; Ravinder Kumar; Milan Kumar Lal; Safina Naz; Rahul Kumar Tiwari (South African Journal of Botany, 2023)

Unraveling the defensive strategies of camel thorn Alhagi maurorum medik. For thriving in arid and semi-arid environments - Ummar Iqbal; Ahmad Ali; Ali Daad; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq; Muhammad Faisal Gul (Journal of Arid Environments, 2023)

Retention of methyl iodide on metal and TEDA impregnated activated carbon using indigenously developed setup - Talhat Yaqoob; Masroor Ahmad; Yasir Faiz; Farman Ali; Amjad Farooq; Faisal Faiz; Attaullah Shah; Muhammad Asim Irshad; Naseem Irfan; Nisar Ali; Sahid Mehmood (Environmental Research, 2023)

Waste heat recovery in iron and steel industry using organic Rankine cycles - Mohammad Ja'fari; Muhammad Imran Khan; Sami G. Al-Ghamdi; Artur J. Jaworski; Faisal Asfand (Chemical Engineering Journal, 2023)

Recent advances in chitosan-based materials; The synthesis, modifications and biomedical applications - Yasir Iqbal; Iqbal Ahmed; Muhammad Faisal Irfan; Shahzad Ali Shahid Chatha; Muhammad Zubair; Aman Ullah (Carbohydrate Polymers, 2023)

Future prospects of biomass waste as renewable source of energy in Pakistan: A mini review - Waqas Ahmad; Jan Nisar; Farooq Anwar; Faisal Muhammad (Bioresource Technology Reports, 2023)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

An Integrated Approach for Biodegradation of Toxic Azo Dyes and Wastewater Recycling by Azoreductase Gene–Harboring Bacillus paramycoides Strain AM-3 - Awais Maqsood; Khola Tazeen; Sabir Hussain; Faisal Mahmood; Muhammad Shahid (Water, Air, & Soil Pollution, 2023)

Impact of different light intensities to Japanese quail eggs on hatching results and post-hatch performance - Shaheryar Ali; Shahid Sherzada; Muhammad Usman; Ehsaan Ullah Khan; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Correction to: Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman Khokhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Levofloxacin–Fatty Acid Systems: Dual Enhancement Through Deep Eutectic Formation and Solubilization for Pharmaceutical Potential and Antibacterial Activity - Bayan Alkhawaja; Faisal Al-Akayleh; Jehad Nasereddin; Suzanne Abdel Malek; Nour Alkhawaja; Muhammad Kamran; Zaid Al-Rubaye; Maisa’a Smairat; Mayyas Al-Remawi; Walid Salem Aburayyan (AAPS PharmSciTech, 2023)

RETRACTED ARTICLE: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Permo-Triassic cyclicity on the western shoulder of Muzaffarabad-Hazara paleo-high, during the oceanisation of Neo-Tethys - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj; Shaukat Ali; Saif ur Rahman; Muhammad Jawad Munawar (Marine and Petroleum Geology, 2023)

Groundwater vulnerability to contamination in the gulf cooperation council region: A review - Faisal Baig; Mohsen Sherif; Ahmed Sefelnasr; Muhammad Abrar Faiz (Groundwater for Sustainable Development, 2023)

Survival tactics of an endangered species Withania coagulans (Stocks) Dunal to arid environments - Ummar Iqbal; Fahad Ur Rehman; Muhammad Usama Aslam; Muhammad Faisal Gul; Umar Farooq; Amina Ameer; Naila Asghar; Ansar Mehmood; Khawaja Shafique Ahmad (Environmental Monitoring and Assessment, 2023)

Geospatial modeling of heterogeneous geotechnical data using conventional and enhanced conception of modified Shepard method-based IDW algorithms: application and appraisal - Zain Ijaz; Cheng Zhao; Nauman Ijaz; Zia ur Rehman; Aashan Ijaz; Muhammad Faisal Junaid (Bulletin of Engineering Geology and the Environment, 2023)

Environmental cost of natural resources, globalization, and economic policy uncertainty in the G-7 bloc: do human capital and renewable energy matter? - Awais Dastgeer; Maria Shabir; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Emerging trends in insect sex pheromones and traps for sustainable management of key agricultural pests in Asia: beyond insecticides—a comprehensive review - Aleena Alam; Sohail Abbas; Arzlan Abbas; Muneer Abbas; Faisal Hafeez; Muhammad Shakeel; Feng Xiao; Chen Ri Zhao (International Journal of Tropical Insect Science, 2023)

First report of Geotrichum candidum causing rose blight disease in Pakistan - Muhammad Talha Ikram; Muhammad Naveed Aslam; Anam Moosa; Faisal Zulfiqar; Muhammad Taimoor Shakeel; Roshaan Ahmed; Muneeb Anwer; Atta ur Rehman Khan (Journal of Plant Pathology, 2023)

Zinc oxide nanoparticles mitigated the arsenic induced oxidative stress through modulation of physio-biochemical aspects and nutritional ions homeostasis in rice (Oryza sativa L.) - Sanaullah Jalil; Suliman M.S. Alghanem; Arwa Abdulkreem AL-Huqail; Muhammad Mudassir Nazir; Faisal Zulfiqar; Temoor Ahmed; Sharafat Ali; Amany H. A. Abeed; Kadambot H.M. Siddique; Xiaoli Jin (Chemosphere, 2023)

Exogenous foliar application of melatonin mitigates salt induced oxidative stress and promotes growth in Gerbera jamosonii - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Muhammad Nafees; Anastasios Darras; Muhammad Mudassir Nazir; Islem Abid; Tarek M.A. Soliman (South African Journal of Botany, 2023)

Cotton and drought stress: An updated overview for improving stress tolerance - Sadia Zafar; Hadiqa Afzal; Areeba Ijaz; Athar Mahmood; Atif Ayub; Airish Nayab; Sadam Hussain; Maqsood UL-Hussan; Muhammad Azeem Sabir; Usman Zulfiqar; Faisal Zulfiqar; Anam Moosa (South African Journal of Botany, 2023)

Examining the role of natural resource rent, environmental regulations, and environmental taxes in sustainable development: Evidence from G-7 economies - Nada Khaddage-Soboh; Adnan Safi; Muhammad Faisal Rasheed; Amir Hasnaoui (Resources Policy, 2023)

Effects of micro(nano)plastics on soil nutrient cycling: State of the knowledge - Muhammad Salam; Huaili Zheng; Yingying Liu; Aneeqa Zaib; Syed Aziz Ur Rehman; Nimra Riaz; Moataz Eliw; Faisal Hayat; Hong Li; Fayuan Wang (Journal of Environmental Management, 2023)

Fabrication of a novel nanocomposite (TiO2/WO3/V2O5) by hydrothermal method as catalyst for hazardous waste treatment - Umer Younas; Awais Ahmad; Aftab Islam; Faisal Ali; Muhammad Pervaiz; Aimon Saleem; Muhammad Waseem; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Salman Raza Naqvi (Fuel, 2023)

Hydrothermal synthesis of V2O5/TiO2 decorated graphitic carbon nitride nanocomposite for biomolecule oxidation inhibition and dye degradation applications - Muhammad Waseem; Awais Ahmad; Muhammad Sagir; Umer Younas; Zohaib Saeed; Muhammad Pervaiz; Faisal Ali; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Rama Rao Karri (Environmental Research, 2023)

Nano priming for boosting growth and resilience in crops under abiotic stresses - Faizan Khalid; Kanza Asif; Yumna Rasheed; Humaira Ashraf; Muhammad Faisal Maqsood; Shamsa Rana; Usman Zulfiqar; Nargis Naz; Muhammad Shahbaz; Rehana Sardar; Zunaira Riaz (Biocatalysis and Agricultural Biotechnology, 2023)

Genome-wide analysis and expression profiling of YUCCA gene family associated with plant vigor in Japanese apricot (prunus mume Sieb. Et zucc) - Faisal Hayat; Yang Bai; Shahid Iqbal; Chengdong Ma; Muhammad Moaaz Ali; Muhammad Adnan Shahid; Mahmood Ul Hasan; Walid F. A. Mosa; Ummara Khan; Huang Xiao; Zhihong Gao (Horticulture, Environment, and Biotechnology, 2023)

Assessing Household’s Municipal Waste Segregation Intentions in Metropolitan Cities of Pakistan: A Structural Equation Modeling Approach - Tanzila Akmal; Faisal Jamil; Muhammad Haseeb Raza; Cosimo Magazzino; Babar Hussain (Environmental Monitoring and Assessment, 2023)
There is a growing concern about inappropriate waste disposal and its negative impact on human health and the environment. The objective of this study is to understand household waste segregation intention considering psychological, institutional, and situational factors simultaneously. Insights into the motivations of household waste segregation drivers may assist in a better knowledge of how to pursue the most efficient and effective initiatives. For this purpose, data from a representative sample comprising 849 households is obtained from the twin cities of Islamabad and Rawalpindi (Pakistan). The empirical analysis employs a Structural Equation Modeling (SEM) approach, showing that policy instruments have significant direct and indirect impacts on households’ segregation intentions. The results highlight that government policy instruments strengthen personal and perceived norms for waste segregation intentions, resulting in an external intervention that would encourage intrinsic motivation. Therefore, policy actions become the main entry point for initiating waste segregation behavior. Public policy must continue to emphasize waste segregation since it may help resource recovery. This is imperative because the environment is a shared resource, and its conservation increases social welfare.

Exogenous melatonin application stimulates growth, photosynthetic pigments and antioxidant potential of white beans under salinity stress - Muhammad Askari; Neelofar Hamid; Zainul Abideen; Faisal Zulfiqar; Anam Moosa; Muhammad Nafees; Ali El-Keblawy (South African Journal of Botany, 2023)

Removal of divalent cations and oxyanions by keratin-derived sorbents: Influence of process parameters and mechanistic studies - Irum Zahara; Muhammad Faisal Irfan; Muhammad Zubair; Tariq Siddique; Aman Ullah (Science of The Total Environment, 2023)

Hollow Mesoporous Silica Nanoparticles for Dual Chemo-starvation Therapy of Hepatocellular Carcinoma - Aftab Ullah; Marina Khan; Zhang Yibang; Faisal Raza; Muhammad Hasnat; Jin Cao; Xueyong Qi; Abid Hussain; Daojun Liu (Pharmaceutical Research, 2023)

Exogenous Application of Moringa Leaf Extract Confers Salinity Tolerance in Sunflower by Concerted Regulation of Antioxidants and Secondary Metabolites - Fozia Farhat; Nadra Ashaq; Ali Noman; Muhammad Aqeel; Shameem Raja; Rashda Naheed; Muhammad Faisal Maqsood; Ijaz Haider; Arneeb Tariq (Journal of Soil Science and Plant Nutrition, 2023)

Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman KhokharVoytas; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Vertical electrical sounding for revealing the groundwater resources in the geothermal spring of Jaboi volcano - Muhammad Yanis; Nasrullah Zaini; Faisal Abdullah; Muhammad Isa; Marwan Marwan; Syafrizal Idris; Andri Yadi Paembonan; Riski Ananda; Muzakir Zainal; Azman Abdul Ghani; Deni Saputra (Acta Geophysica, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Natural resources revenues, shadow economy and financial institutions depth: The way forward - Faryal; Faisal Faisal; Muhammad Yusuf Amin; Zahoor Ul Haq; Sami Ur Rahman; Adnan Ali (Resources Policy, 2023)

Barriers to the adoption of social welfare measures in the electricity tariff structure of developing countries: A case of Pakistan - Muhammad Zain Jan; Kafait Ullah; Faisal Abbas; Hassan Abdullah Khalid; Tariq M. Bajwa (Energy Policy, 2023)

Proline Alleviates Abiotic Stress Induced Oxidative Stress in Plants - Faisal Zulfiqar; Muhammad Ashraf (Journal of Plant Growth Regulation, 2023)

Anti-arthritic effects of geranium essential oil loaded chitosan nanoparticles in Freund’s complete adjuvant induced arthritic rats through down-regulation of inflammatory cytokines - Rana Dawood Naseer; Faqir Muhammad; Bilal Aslam; Muhammad Naeem Faisal (Inflammopharmacology, 2023)

RETRACTED ARTICLE: The role of monetary and fiscal policies in determining environmental pollution: Revisiting the N-shaped EKC hypothesis for China - Tang Zhengxia; Mohammad Haseeb; Muhammad Usman; Mohd Shuaib; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Impact of biochar amendments on copper mobility, phytotoxicity, photosynthesis and mineral fluxes on (Zea mays L.) in contaminated soils - Zainul Abideen; Hans-Werner Koyro; Faisal Zulfiqar; Anam Moosa; Sarwat Ghulam Rasool; Muhammad Zaheer Ahmad; Muhammad Ahsan Altaf; Nadia Sharif; Ali El-Keblawy (South African Journal of Botany, 2023)

Current status of CO2 capture with ionic liquids: Development and progress - Wamda Faisal Elmobarak; Fares Almomani; Muhammad Tawalbeh; Amani Al-Othman; Remston Martis; Kashif Rasool (Fuel, 2023)

Sublethal effects of spinetoram and emamectin benzoate on key demographic parameters of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory conditions - Arzlan Abbas; Chen Ri Zhao; Muhammad Arshad; Xiao Han; Ayesha Iftikhar; Faisal Hafeez; Asad Aslam; Farman Ullah (Environmental Science and Pollution Research, 2023)

Entrepreneurship and universities pedagogical perspectives and philosophies - Arman; Muhammad Ali Faisal; Saiful Anwar (The Social Science Journal, 2023)

Exogenous melatonin alleviates cadmium-induced inhibition of growth and photosynthesis through upregulating antioxidant defense system in strawberry - Muhammad Saqib; Umbreen Shahzad; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Safina Naz; Mohammad Shah Jahan; Zoia Arshad Awan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (South African Journal of Botany, 2023)

Mineralogy and PGE geochemistry of chromitites and peridotites of the sapat complex in the indus suture zone, northern Pakistan: implications for magmatic processes in the supra-subduction zone - Zaheen Ullah; Huan Li; Asad Khan; Shah Faisal; Yildirim Dilek; Michael W. Förster; Muhammad Farhan; Umar Ashraf; Salman Ahmed Khattak; Gohar Rehman; Syed Asim Hussain (International Geology Review, 2023)

Natural resources, fiscal decentralization, and environmental quality in China: an empirical analysis from QARDL approach - Mei Zhang; Muhammad Hafeez; Chaudhry Muhammad Nadeem Faisal; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Integrating wheat straw and silica fume as a balanced mechanical ameliorator for expansive soil: a novel agri-industrial waste solution - Usama Khalid; Zia ur Rehman; Nauman Ijaz; Inamullah Khan; Muhammad Faisal Junaid (Environmental Science and Pollution Research, 2023)

First record of Fusarium solani causing post-harvest Fusarium rot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Faisal Zulfiqar; Muhammad Naveed Aslam (Journal of Plant Pathology, 2023)

Application of QPPO/PVA based commercial anion exchange membrane as an outstanding adsorbent for the removal of Eosin-B dye from wastewaters - Muhammad Imran Khan; Abdallah Shanableh; Akram M. Alfantazi; Mushtaq Hussain Lashari; Suryyia Manzoor; Ramsha Anwer; Nosheen Farooq; Farid A. Harraz; Mabkhoot Alsaiari; M. Faisal (Chemosphere, 2023)

Modification in cellulose films through ascent cold plasma treatment and polymerization for food products packaging - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Rana Muhammad Aadil; Muhammad Faisal Manzoor; Jun-Hu Cheng (Trends in Food Science & Technology, 2023)

Remediation methods of heavy metal contaminated soils from environmental and geotechnical standpoints - Zia ur Rehman; Muhammad Faisal Junaid; Nauman Ijaz; Usama Khalid; Zain Ijaz (Science of The Total Environment, 2023)

Natural pigments: Anthocyanins, carotenoids, chlorophylls, and betalains as colorants in food products - Brera Ghulam Nabi; Kinza Mukhtar; Waqar Ahmed; Muhammad Faisal Manzoor; Muhammad Modassar Ali Nawaz Ranjha; Marek Kieliszek; Zuhaib F. Bhat; Rana Muhammad Aadil (Food Bioscience, 2023)

Challenges associated with cellulose composite material: Facet engineering and prospective - Tariq Aziz; Fazal Haq; Arshad Farid; Mehwish Kiran; Shah Faisal; Asmat Ullah; Naveed Ullah; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; Pau Loke Show (Environmental Research, 2023)

Role of silica-based porous cellulose nanocrystals in improving water absorption and mechanical properties - Tariq Aziz; Arshad Farid; Fazal Haq; Mehwish Kiran; Naveed Ullah; Shah Faisal; Amjad Ali; Farman Ullah Khan; Siming You; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Environmental Research, 2023)

A New Regional Drought Index under X-bar Chart Based Weighting Scheme – The Quality Boosted Regional Drought Index (QBRDI) - Zulfiqar Ali; Sadia Qamar; Nasrulla Khan; Muhammad Faisal; Saad Sh. Sammen (Water Resources Management, 2023)

Recyclable Cu–Ag bimetallic nanocatalyst for radical scavenging, dyes removal and antimicrobial applications - Faisal Ali; Sadia Akbar; Mika Sillanpaa; Umer Younas; Adnan Ashraf; Muhammad Pervaiz; Rizwan Kausar; Ikram Ahmad; Asma A. Alothman; Mohamed Ouladsmane (Chemosphere, 2023)

Comparison of pixel, sub-pixel and object-based image analysis techniques for co-seismic landslides detection in seismically active area in Lesser Himalaya, Pakistan - Sumbal Bahar Saba; Muhammad Ali; Syed Ali Turab; Muhammad Waseem; Shah Faisal (Natural Hazards, 2023)

Geochemistry and in-situ U-Th/Pb Geochronology of the Jambil Meta-Carbonatites, Northern Pakistan: Implications on Petrogenesis and Tectonic Evolution - Asad Khan; Shah Faisal; Kyle P. Larson; Delores M. Robinson; Huan Li; Zaheen Ullah; Mark Button; Javed Nawab; Muhammad Farhan; Liaqat Ali; Muhammad Ali (Journal of Earth Science, 2023)

An integrated investigation of hydrocarbon pollution in Ahoada area, Niger Delta Region, Nigeria - Hafiz Aminu Umar; Mohd Faisal Abdul Khanan; Mohammed Sanusi Shiru; Anuar Ahmad; Muhammad Zulkarnain Abdul Rahman; Ami Hassan Md din (Environmental Science and Pollution Research, 2023)

Hydrogen Production through Water Vapors using Optimized Corona-DBD Hybrid Plasma Micro-Reactor - Muhammad Younas; Sumeer Shafique; Abrar Faisal; Ainy Hafeez; Fahed Javed; Maria Mustafa; Fahad Rehman (Fuel, 2023)

WS2-embedded MXene/GO hybrid nanosheets as electrodes for asymmetric supercapacitors and hydrogen evolution reactions - Sajjad Hussain; Dhanasekaran Vikraman; Zulfqar Ali Sheikh; Muhammad Taqi Mehran; Faisal Shahzad; Khalid Mujasam Batoo; Hyun-Seok Kim; Deok-Kee Kim; Muhammad Ali; Jongwan Jung (Chemical Engineering Journal, 2023)

Spatio-temporal assessment of land use land cover based on trajectories and cellular automata Markov modelling and its impact on land surface temperature of Lahore district Pakistan - Aqil Tariq; Faisal Mumtaz; Muhammad Majeed; Xing Zeng (Environmental Monitoring and Assessment, 2023)

Heavy metal(loid)s contamination and potential risk assessment via groundwater consumption in the district of Hangu, Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Environmental Science and Pollution Research, 2022)

Comparative Assessment of Remediation Potential of Xanthium strumarium Ecotypes in NaCl-Affected Root Zone - Noreen Akhter; Muhammad Aqeel; Muhammad Faisal Maqsood; Saher Nawaz; Muhammad Muslim Shahnaz; Noreen Khalid; Mohammed A. Basahi; Omar Mahmoud Al-Zoubi; Talaat Habeeb; Romina Alina Marc; Muhammad Kashif Irshad; Ali Noman (Water, Air, & Soil Pollution, 2022)

Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Exploration of solid waste materials for sustainable manufacturing of cementitious composites - Hamayun Khan; Anwar Baig; Mahtab Faisal; Adnan Khan; Kashif Gul; Nauman Ali; Nisar Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Correction: Fazal et al. Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions. J. Mar. Sci. Eng. 2022, 10, 800 - Abdul Ghaffar Fazal; Muhammad Umar; Faisal Shah; Muhammad Armaghan Faisal Miraj; Hammad Tariq Janjuhah; George Kontakiotis; Abdul Khaliq Jan (Journal of Marine Science and Engineering, 2022)
In the original publication [...]

Variation in Vortex-Induced Vibration Phenomenon Due to Surface Roughness on Low- and High-Mass-Ratio Circular Cylinders: A Numerical Study - Muhammad Usman Anwar; Niaz Bahadur Khan; Muhammad Arshad; Adnan Munir; Muhammad Nasir Bashir; Mohammed Jameel; Muhammad Faisal Rehman; Sayed M. Eldin (Journal of Marine Science and Engineering, 2022)
Fluid–structure interaction has been widely studied in the last few decades due to its wide range of applications in engineering fields. This phenomenon plays an important design role, for example, in offshore risers, high slender buildings, chimney stacks and heat exchangers. The vortex shedding generated from a bluff body can induce high-amplitude oscillations, known as vortex-induced vibrations (VIVs). This study presents a numerical analysis to investigate the impact of surface roughness on VIV in the crossflow direction of a circular cylinder. The study also investigates the impact of surface roughness with variation in mass ratio from 2.4 to 11 at a high Reynolds number (Re) = 104 using Reynolds-averaged Navier–Stokes (RANS) equations. The study concludes that roughness on a cylinder results in a reduction in amplitude response. Furthermore, the lock-in region is narrower compared to that of a smooth cylinder, irrespective of the mass ratio. However, it is observed that the impact of surface roughness is more significant in high-mass-ratio cylinders where the lock-in region is more squeezed and shifted toward lower reduced velocities. Furthermore, the vortex mode beyond reduced velocities Ur = 5.84 and 7.52 was observed to be 2S for high and low mass ratios, respectively.

Effects of maize silage substitution with sugarbeet or citrus pulp ensiled with corncobs on growth performance, digestibility, and economic benefits in buffalo calves - Muhammad Iqbal Anjum; Shahbaz Javaid; Faisal Ashfaq; Javed Iqbal (Tropical Animal Health and Production, 2022)

Correction to: Awareness regarding COVID‑19 and its effects on mental health among pre‑professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

Awareness regarding COVID-19 and its effects on mental health among pre-professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

Mediation of Growth and Metabolism of Pisum sativum in Salt Stress Potentially Be Credited to Thiamine - Rashda Naheed; Maryeum Zahid; Muhammad Aqeel; Muhammad Faisal Maqsood; Hina Kanwal; Noreen Khalid; Mohamed Hashem; Saad Alamri; Ali Noman (Journal of Soil Science and Plant Nutrition, 2022)

Assessment and source apportionment of water-soluble heavy metals in road dust of Zhengzhou, China - Muhammad Faisal; Zening Wu; Huiliang Wang; Zafar Hussain; Muhammad Imran Azam; Muhammad Muzammil (Environmental Science and Pollution Research, 2022)

Sulfur concrete made with waste marble and slag powders: 100% recycled and waterless concrete - Muhammad Faisal Rasheed; Abdur Rahim; Muhammad Irfan-ul-Hassan; Babar Ali; Nazam Ali (Environmental Science and Pollution Research, 2022)

Effect of co-fermentation system with isolated new yeasts on soymilk: microbiological, physicochemical, rheological, aromatic, and sensory characterizations - Sameh A. Korma; Li Li; Mohamed Ghamry; Qiyang Zhou; Peipei An; Khaled A. E. Abdrabo; Muhammad Faisal Manzoor; Abdur Rehman; Sobia Niazi; Ilaria Cacciotti (Brazilian Journal of Microbiology, 2022)

A comparative analysis of pre- and post-industrial spatiotemporal drought trends and patterns of Tibet Plateau using Sen slope estimator and steady-state probabilities of Markov Chain - Zhenya Li; Zulfiqar Ali; Tong Cui; Sadia Qamar; Muhammad Ismail; Amna Nazeer; Muhammad Faisal (Natural Hazards, 2022)

Adrenergic blocker terazosin potentially suppresses acetaminophen induced-acute liver injury in animal models via CYP2E1 gene - Zoya Hashmat; Iffat Saeed Channa; Muhammad Safdar; Mehmet Ozaslan; Muhammad Saeed; Faisal Siddique; Yasmeen Junejo (Toxicological Research, 2022)

Acacia jacquemontii ethyl acetate extract reduces hyperglycemia and pro-inflammatory markers while increasing endogenous antioxidant potential in alloxan-induced diabetic rats - Ambreen Mehmood Awan; Wafa Majeed; Faqir Muhammad; Muhammad Naeem Faisal (Environmental Science and Pollution Research, 2022)

Energy-levels well-matched direct Z-scheme ZnNiNdO/CdS heterojunction for elimination of diverse pollutants from wastewater and microbial disinfection - Muhammad Shahid Nadeem; Tauseef Munawar; Faisal Mukhtar; Sana Batool; Murtaza Hasan; Usman Ali Akbar; Abbas Saeed Hakeem; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Geological mapping and neo-tectonics studies of the eocene limestone distributed over Mala Khel Anticline, Trans Indus ranges, North-West Himalayas, Pakistan - Nazir-ur- Rehman; Sajjad Ahmad; Shah Faisal; Asghar Ali; Muhammad Waqar Azeem; Afrasiab; Shuja Ullah; Salik Javed (Arabian Journal of Geosciences, 2022)

Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions - Abdul Fazal; Muhammad Umar; Faisal Shah; Muhammad Miraj; Hammad Janjuhah; George Kontakiotis; Abdul Jan (Journal of Marine Science and Engineering, 2022)
The geochemical investigation of shales from the Early to Middle Cretaceous Chichali Formation in the Hazara Basin was conducted to determine the origin, tectonic setting and evolution, paleo-weathering conditions, and paleo-oceanographic reconstruction. The research included a comprehensive field survey, sample collection, and analysis of a variety of main, trace, and rare-earth elements using an X-ray fluorescence spectrometer (XRF). Bivariate plots and ternary diagrams were used to determine the provenance, tectonic setting, and paleo-weathering conditions that existed during the development of the Chichali Formation in the Hazara Basin. The values of Ba/Sc, Ba/Co, Th/Sc, Cr/Th, Cr/Zr, Th/Co, Th/Cr, Sc/Th, bivariate plots of Al2O3 vs. TiO2, TiO2 vs. Zr, TiO2 vs. Ni, Df1–Df2, Zr vs. Nb, and La/Sc vs. Th/Co, and ternary diagram of K2O–Fe2O3–Al2O3 were used to illustrate the passive continental margin setting of Chichali Formation shales. The detailed chemical analysis also provides an understanding of the marine geochemical cycle, which reflects the origin of these sediments. The average K2O/Al2O3 value is less than 0.4, indicating that the shale contains clay minerals. The Chichali Formation’s Chemical Index of Alteration (mean = 71) and Index of Compositional Variation (mean = 1.12) values show a modest degree of chemical weathering in the source locations. From an environmental standpoint, the Chichali Formation is richer in toxic elements such as Ba, Zn, Ni, Cr, and Cu, which may be damaging to agricultural soils and drinking water when present in excess. These metals are incorporated into the formation during the weathering process.

Influences of Long-term Crop Cultivation and Fertilizer Management on Soil Aggregates Stability and Fertility in the Loess Plateau, Northern China - Farhat Ullah Khan; Adnan Anwar Khan; Kai Li; Xuexuan Xu; Muhammad Adnan; Shah Fahad; Rafiq Ahmad; Mushtaq Ahmad Khan; Taufiq Nawaz; Faisal Zaman (Journal of Soil Science and Plant Nutrition, 2022)

Geochemical characteristics of coal seams within the Paleocene Patala Formation, Central Salt Range coal mines (Punjab), Northern Pakistan - Muhammad Sajid; Natasha Khan; Faisal Shah; Muhammad Kashif; Shaukat Khan (Journal of Sedimentary Environments, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

Enhancing wheat-flour safety by detecting and controlling red flour beetle Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) - Fuqiang Gao; Yajing Qi; Alkassoumi Hassane Hamadou; Jiyao Zhang; Muhammad Faisal Manzoor; Qin Guo; Bin Xu (Journal of Consumer Protection and Food Safety, 2022)

Factors associated with cycle threshold values (Ct-values) of SARS-CoV2-rRT-PCR - Naila Shoaib; Naila Noureen; Arwa Faisal; Muhammad Zaheer; Muhammad Imran; Ali Ahsan; Rimsha Munir; Nousheen Zaidi (Molecular Biology Reports, 2022)

Associations of air pollution concentrations and energy production dynamics in Pakistan during lockdown - Sawaid Abbas; Ghaffar Ali; Faisal Mueen Qamer; Syed Muhammad Irteza (Environmental Science and Pollution Research, 2022)

Effects of replacement of wheat straw with corn stover-based TMR on growth performance, behavioral characteristics, selected blood metabolites, and nutrient digestibility in Beetal bucks - Faisal Majeed; Saeed Ahmed; Muhammad Afzal Rashid; Muhammad Qamar Shahid; Imran Mohsin (Tropical Animal Health and Production, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Habitat characterization of Aedes albopictus - Faisal Hafeez; Unsar Naeem-Ullah; Waseem Akram; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Muhammad Jawad Saleem (International Journal of Tropical Insect Science, 2022)

Susceptibility of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) on detached plant parts of transgenic and non-transgenic cotton - Muhammad Jawad Saleem; Faisal Hafeez; Qurban Ali; Asad Aslam; Muhammad Arshad; Dilbar Hussain; Ayesha Iftikhar; Afifa Naeem; Muhammad Saleem (International Journal of Tropical Insect Science, 2022)

Malignancy risk in individuals with familial adenomatous polyposis receiving biologics and immunomodulators - Muhammad Salman Faisal; Carol A. Burke; Jean-Paul Achkar; Benjamin Click; Margaret O’Malley; Lisa LaGuardia; Susan Milicia; Brandie Leach; David Liska; James Church; Matthew Kalady; Gautam Mankaney (Familial Cancer, 2022)

Strauss point modeling for seismic activity: a case study of earthquakes - Amna Zahra; Ijaz Hussain; Muhammad Zaffar Hashmi; Muhammad Faisal; Elsayed Elsherbini Elashkar; Sadaf Shamshoddin Soudagar; Fares Fawzi Al-Deek; Mohammed Ageli (Modeling Earth Systems and Environment, 2022)

Cadmium Toxicity in Plants: Recent Progress on Morpho-physiological Effects and Remediation Strategies - Usman Zulfiqar; Aqsa Ayub; Saddam Hussain; Ejaz Ahmad Waraich; Mohamed A. El-Esawi; Muhammad Ishfaq; Muhammad Ahmad; Nauman Ali; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2022)

A comparative Appraisal of Classical and Holistic Water Scarcity Indicators - Zafar Hussain; Zongmin Wang; Jiaxue Wang; Haibo Yang; Muhammad Arfan; Daniyal Hassan; Wusen Wang; Muhammad Imran Azam; Muhammad Faisal (Water Resources Management, 2022)

Shallow Structure Fault and Fracture Mapping in Jaboi Volcano, Indonesia, Using VLF–EM and Electrical Resistivity Methods - Muhammad Yanis; Nazli Ismail; Faisal Abdullah (Natural Resources Research, 2022)

Insect pests of economic importance attacking wheat crop (Triticum aestivum L.) in Punjab, Pakistan - Dilbar Hussain; Muhammad Asrar; Bushra Khalid; Faisal Hafeez; Muhammad Saleem; Muazzma Akhter; Maqsood Ahmed; Imran Ali; Kanwal Hanif (International Journal of Tropical Insect Science, 2022)

Using a smartphone on the move: do visual constraints explain why we slow walking speed? - Alejandro Rubio Barañano; Muhammad Faisal; Brendan T. Barrett; John G. Buckley (Experimental Brain Research, 2022)
Viewing one’s smartphone whilst walking commonly leads to a slowing of walking. Slowing walking speed may occur because of the visual constraints related to reading the hand-held phone whilst in motion. We determine how walking-induced phone motion affects the ability to read on-screen information. Phone-reading performance (PRP) was assessed whilst participants walked on a treadmill at various speeds (Slow, Customary, Fast). The fastest speed was repeated, wearing an elbow brace (Braced) or with the phone mounted stationary (Fixed). An audible cue (‘text-alert’) indicated participants had 2 s to lift/view the phone and read aloud a series of digits. PRP was the number of digits read correctly. Each condition was repeated 5 times. 3D-motion analyses determined phone motion relative to the head, from which the variability in acceleration in viewing distance, and in the point of gaze in space in the up-down and right-left directions were assessed. A main effect of condition indicated PRP decreased with walking speed; particularly so for the Braced and Fixed conditions ( p = 0.022). Walking condition also affected the phone’s relative motion ( p < 0.001); post-hoc analysis indicated that acceleration variability for the Fast, Fixed and Braced conditions were increased compared to that for Slow and Customary speed walking ( p ≤ 0.05). There was an inverse association between phone acceleration variability and PRP ( p = 0.02). These findings may explain why walking speed slows when viewing a hand-held phone: at slower speeds, head motion is smoother/more regular, enabling the motion of the phone to be coupled with head motion, thus making fewer demands on the oculomotor system. Good coupling ensures that the retinal image is stable enough to allow legibility of the information presented on the screen.

Does ICT diffusion lead to energy efficiency and environmental sustainability in emerging Asian economies? - Shufang Zhao; Muhammad Hafeez; Chaudhry Muhammad Nadeem Faisal (Environmental Science and Pollution Research, 2022)

Bacterial prediction using internet of things (IoT) and machine learning - Hamza Khurshid; Rafia Mumtaz; Noor Alvi; Ayesha Haque; Sadaf Mumtaz; Faisal Shafait; Sheraz Ahmed; Muhammad Imran Malik; Andreas Dengel (Environmental Monitoring and Assessment, 2022)

Paleostress inversion and outcrop fracture analysis of the brittle deformation along Main Boundary Thrust (MBT), NW Himalaya, Pakistan - Naveed Ahsan; Hassan Mehmood; Muhammad Armaghan Faisal Miraj; Iqra Bano; Abdul Qayyum; Rana Faizan Saleem (Journal of Earth System Science, 2021)

Assessment of Microscopic Detection of Malaria with Nested Polymerase Chain Reaction in War-Torn Federally Administered Tribal Areas of Pakistan - Muhammad Faisal Nadeem; Aamer Ali Khattak; Nadia Zeeshan; Usman Ayub Awan; Adnan Yaqoob (Acta Parasitologica, 2021)

Petrogenesis of the peralkaline Dutsen Wai and Ropp complexes in the Nigerian younger granites: implications for crucial metal enrichments - Abdulgafar Kayode Amuda; Xiaoyong Yang; Jianghong Deng; Mohamed Faisal; Jinya Cao; Saleh Ibrahim Bute; Musa Bala Girei; Safiyanu Muhammad Elatikpo (International Geology Review, 2021)

Reduction of Errors in Hydrological Drought Monitoring – A Novel Statistical Framework for Spatio-Temporal Assessment of Drought - Zulfiqar Ali; Asad Ellahi; Ijaz Hussain; Amna Nazeer; Sadia Qamar; Guangheng Ni; Muhammad Faisal (Water Resources Management, 2021)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

Challenges and prospects for a potential allohexaploid Brassica crop - Kangni Zhang; Annaliese S. Mason; Muhammad A. Farooq; Faisal Islam; Daniela Quezada-Martinez; Dandan Hu; Su Yang; Jun Zou; Weijun Zhou (Theoretical and Applied Genetics, 2021)

Expression of DnMTs and MBDs in AlCl3-Induced Neurotoxicity Mouse Model - Muhammad Faisal Ikram; Syeda Mehpara Farhat; Aamra Mahboob; Saeeda Baig; Ahmed Yaqinuddin; Touqeer Ahmed (Biological Trace Element Research, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

Sunlight-induced photocatalytic degradation of various dyes and bacterial inactivation using CuO–MgO–ZnO nanocomposite - Tauseef Munawar; Faisal Mukhtar; Sadaf Yasmeen; Muhammad Naveed-ur-Rehman; Muhammad Shahid Nadeem; Muhammad Riaz; Muhammad Mansoor; Faisal Iqbal (Environmental Science and Pollution Research, 2021)

A novel framework for regional pattern recognition of drought intensities - Rizwan Niaz; Ijaz Hussain; Zulfiqar Ali; Muhammad Faisal (Arabian Journal of Geosciences, 2021)

Identification and inter‐comparison of appropriate long‐term precipitation datasets using decision tree model and statistical matrix over China - Muhammad Abrar Faiz; Yongqiang Zhang; Faisal Baig; Dariusz Wrzesiński; Farah Naz (International Journal of Climatology, 2021)
The reliability of long‐term precipitation estimates is vital for climatology and hydrometeorology applications. Different climatic zones and high rain gauge network (more than 800) of China are a suitable topography for performance evaluation of different long‐term precipitation datasets. In this study, seven long‐term precipitation datasets are tested against in situ observations at different time scales (1981–2016) at 813 grid points. Well‐known statistical indicators and Fast‐frugal tree (FFt) decision model are employed to identify the best long‐term datasets. Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks Climate Data Record is the only datasets that did not perform well in the study area. Asian Precipitation‐Highly‐Resolved Observational Data Integration Towards Evaluation (APHRODITE), Global Precipitation Climatology Centre (GPCC), and Climate Prediction Center (CPC‐Global) estimates are comparable with in situ observations. Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), National Centers for Environmental Prediction (NCEP2) overestimate the precipitation extremes in the region. There exists a difference of 100–250 mm among precipitation datasets at an annual scale. All of the seven long‐term datasets underestimate the rxdays across China. The minimum range of rxdays (maximum precipitation amount in under defined days: 1 day or 5 days) captured by datasets is comparable except PERSIANN‐CDR. The maximum range calculated with PERSIANN‐CDR is 55.01 (rx1day), and 129.67 (rx5day), much less than the in situ rxdays. This analysis shows that datasets failed to capture maximum precipitation intensity in the region as well. FFt decision model results show that APHRODITE ranked first based on calculated consecutive dry days among all six other datasets in the most climatic zones. Overall, results indicate that data assimilation, the spatial coverage of ground stations, and interpolation techniques used to develop the datasets may limit the reliability of precipitation datasets in the study area.

Wind speed pattern data and wind energy potential in Pakistan: current status, challenging platforms and innovative prospects - Hammad Saulat; Muhammad Masood Khan; Muhammad Aslam; Muhammad Chawla; Sikander Rafiq; Faisal Zafar; Muhammad Mahmood Khan; Awais Bokhari; Farrukh Jamil; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2021)

Clove (Syzygium aromaticum) and its phytochemicals in ruminant feed: an updated review - Muhammad Saeed; Muhammad S. Khan; Mahmoud Alagawany; Mayada R. Farag; Othman Alqaisi; Amjad I. Aqib; Muhammad Qumar; Faisal Siddique; Mohamed Fawzy Ramadan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

An integrated approach to evaluate the unconventional hydrocarbon generation potential of the Lower Goru Formation (Cretaceous) in Southern Lower Indus basin, Pakistan - Muhsan Ehsan; Hanming Gu; Abid Ali; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Muhammad Armaghan Faisal Miraj; Munawar Shah (Journal of Earth System Science, 2021)

Dusky cotton bug Oxycarenus hyalinipennis Costa (Lygaeidae: Hemiptera) loss assessment in cotton - Faisal Hafeez; Muhammad Akram; Muhammad Farooq; Muhammad Saghir; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Unsar Naeem-Ullah (International Journal of Tropical Insect Science, 2021)

Comparative efficacy of biogenic zinc oxide nanoparticles synthesized by Pseudochrobactrum sp. C5 and chemically synthesized zinc oxide nanoparticles for catalytic degradation of dyes and wastewater treatment - Khadija Siddique; Muhammad Shahid; Tanvir Shahzad; Faisal Mahmood; Habibullah Nadeem; Muhammad Saif ur Rehman; Sabir Hussain; Omer Sadak; Sundaram Gunasekaran; Tahseen Kamal; Ikram Ahmad (Environmental Science and Pollution Research, 2021)

The northernmost part of the Great Sumatran Fault map and images derived from gravity anomaly - Muhammad Yanis; Faisal Abdullah; Nasrullah Zaini; Nazli Ismail (Acta Geophysica, 2021)

Modeling and forecasting of principal minerals production - Sunila Saadat; Ijaz Hussain; Muhammad Faisal (Arabian Journal of Geosciences, 2021)

Engineering aspect of sustainability assessment for geotechnical projects - Faisal Raza; Badee Alshameri; S. Muhammad Jamil (Environment, Development and Sustainability, 2021)

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

Impact of light stimulation during incubation on hatching traits and post-hatch performance of commercial broilers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Abd ur Rehman; Muhammad Usman; Shahid Mehmood; Sohail Ahmad (Tropical Animal Health and Production, 2021)

Effects of soil application of two different fipronil formulations on some soil-dwelling non-target arthropods - Muhammad Asad; Sohail Ahmed; Rashad Rasool Khan; Abid Ali; Muhammad Fahad Raza; Ammarah Shabbir; Faisal Munir; Anam Noreen Abbas; Mubashir Tariq (International Journal of Tropical Insect Science, 2021)

Farmers’ perception and adaptations to climate change: findings from three agro-ecological zones of Punjab, Pakistan - Muhammad Faisal Ali; Sobia Rose (Environmental Science and Pollution Research, 2021)

Proposed formulation of surface water quality and modelling using gene expression, machine learning, and regression techniques - Muhammad Izhar Shah; Muhammad Faisal Javed; Taher Abunama (Environmental Science and Pollution Research, 2021)

Assessment of triple bottom line of sustainability for geotechnical projects - Faisal Raza; Badee Alshameri; S. Muhammad Jamil (Environment, Development and Sustainability, 2021)

Calotetrapterins A-C, three new pyranoxanthones and their cytotoxicity from the stem bark of Calophyllum tetrapterum Miq - Mulyadi Tanjung; Tjitjik Srie Tjahjandarie; Ratih Dewi Saputri; Baharrani Dwi Kurnia; Muhammad Faisal Rachman; Yana Maolana Syah (Natural Product Research, 2021)

Exploring the role of fossil fuels, hydroelectricity consumption, and financial sector in ensuring sustainable economic development in the emerging economy - Faisal Faisal; Muhammad Numan Khan; Ruqiya Pervaiz; Peshraw Majid Muhamad; Mohammad Othman Jamil Rashdan (Environmental Science and Pollution Research, 2021)

Study of the nonlinear character of ionospheric signals possessing critical frequency (foF2) at Pakistan air space - Bulbul Jan; Faisal Ahmed Khan Afridi; Muhammad Ali; Muhammad Ayub Khan Yousufzai (Arabian Journal of Geosciences, 2021)

Bioregulators: unlocking their potential role in regulation of the plant oxidative defense system - Faisal Zulfiqar; Muhammad Ashraf (Plant Molecular Biology, 2021)

Zinc Application in Combination with Zinc Solubilizing Enterobacter sp. MN17 Improved Productivity, Profitability, Zinc Efficiency, and Quality of Desi Chickpea - Aman Ullah; Muhammad Farooq; Faisal Nadeem; Abdul Rehman; Mubshar Hussain; Ahmad Nawaz; Muhammad Naveed (Journal of Soil Science and Plant Nutrition, 2020)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Molecular identification of sugarcane black bug (Cavelarius excavates) from Pakistan using cytochrome C oxidase I (COI) gene as DNA barcode - Khadim Hussain; Kamran Rashid; Faisal Hafeez; Ikrma Amad; Muhammad Ashraf (International Journal of Tropical Insect Science, 2020)

Oral supplementation of Ficus religiosa leaf extract adversely affects the selected behavioral aspects of male albino mice - Naheed Akhtar; Shahid Iqbal; Muhammad Faisal Shahzad; Muhammad Latif; Furhan Iqbal (Biologia, 2020)

Investment profitability and economic efficiency of the drip irrigation system: Evidence from Egypt * - Abdelrahman Ali; Chunping Xia; Cheng Jia; Muhammad Faisal (Irrigation and Drainage, 2020)
Modern irrigation systems are key to improving the productivity of water and land units. This study assesses the economic aspects of the drip irrigation system (DIS) by calculating the investment profitability and economic efficiency of the DIS for growing tomatoes in Egypt. One hundred tomato farmers were surveyed. Financial discounted criteria were used in addition to data envelopment analysis to estimate the economic efficiency of growing tomatoes using the DIS. The results showed that investment in the DIS is lucrative, with an increase of 67% in the net return per hectare, compared with results using non‐drip irrigation. The benefit–cost ratio amounted to 1.35, the net present value was US$1720, and the internal rate of return was 44%. The data envelopment analysis results revealed that most farms achieved technical and allocative efficiencies; however, cost and scale efficiencies still need improvement. These results could guide policymakers when designing irrigation transformation strategies that involve the use of micro‐credit to encourage small farmers to change from conventional irrigation systems to DISs. Agricultural extension agencies should organize intensive training programmes for small farmers on how to operate and maintain the DIS. These policies will accelerate the adoption of irrigation modernization and help vulnerable farmers maximize productivity and achieve sustainability in the use of limited resources.

Evaluation of rapid polymyxin Nordmann Poirel test for detection of polymyxin resistance in clinical isolates of Enterobacteriaceae - Muhammad Shoaib; Ashfaq Hussain; Luqman Satti; Wajid Hussain; Gohar Zaman; Faisal Hanif (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Modeling smallholder livestock herders’ intentions to adopt climate smart practices: An extended theory of planned behavior - Muhammad Faisal; Xia Chunping; Shoaib Akhtar; Muhammad Haseeb Raza; Muhammad Tariq Iqbal Khan; Muhammad Arslan Ajmal (Environmental Science and Pollution Research, 2020)

Heterologous expression of azoreductase-encoding gene azrS of Bacillus sp. MR-1/2 for enhanced azo dye decolorization and wastewater treatment - Ali Abbas; Aqsa Mushtaq; Ayesha Iftikhar Cheema; Faisal Mahmood; Muhammad Asaf Khan; Tahir Naqqash; Mohsin Khurshid; Irfan Manzoor; Sher Muhammad; Muhammad Shahid (Archives of Microbiology, 2020)

Correction to: Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

Comparative Assessment of Reference Evapotranspiration Estimation Using Conventional Method and Machine Learning Algorithms in Four Climatic Regions - Ali Raza; Muhammad Shoaib; Muhammad Abrar Faiz; Faisal Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah; Muhammad Zubair (Pure and Applied Geophysics, 2020)

Correction to: Sublethal effects of a juvenile hormone analog, Pyriproxyfen demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Sublethal effects of a juvenile hormone analog, Pyriproxyfen on demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

Application of a Dye-Decolorizing Pseudomonas aeruginosa Strain ZM130 for Remediation of Textile Wastewaters in Aerobic/Anaerobic Sequential Batch Bioreactor and Soil Columns - Zahid Maqbool; Muhammad Shahid; Farrukh Azeem; Tanvir Shahzad; Faisal Mahmood; Muzammal Rehman; Tanvir Ahmed; Muhammad Imran; Sabir Hussain (Water, Air, & Soil Pollution, 2020)

Taxonomic assessment of the Malayan water shrew Chimarrogale hantu Harrison, 1958 and reclassification to the genus Crossogale - Muhammad Farhan Abd Wahab; Dharini Pathmanathan; Masaharu Motokawa; Faisal Ali Anwarali Khan; Hasmahzaiti Omar (Mammalian Biology, 2020)

A novel nonsense mutation in NPR2 gene causing Acromesomelic dysplasia, type Maroteaux in a consanguineous family in Southern Punjab (Pakistan) - Saima Mustafa; Zafrin Akhtar; Muhammad Latif; Mubashir Hassan; Muhammad Faisal; Furhan Iqbal (Genes & Genomics, 2020)
Background Acromesomelic dysplasia, type Maroteaux (AMDM) is a rare skeletal dysplasia following autosomal recessive mode of inheritance and characterized by abnormal growth plates, short and abnormal bones in the extremities and spine. Objective Present study was designed to report the molecular basis of AMDM in enrolled consanguineous family from Pakistan. Methods A consanguineous family from Vehari District in Pakistan having multiple siblings suffering from AMDM was enrolled in present study. Whole exome sequencing (WES) approach was adopted to identify causative agent of AMDM. Human full length NPR2 gene and sequence with nonsense mutation was amplified by using Myc-tagged pXN vector and transformed in E. coli DH5α cells to confirm mutation. SDS-PAGE and Western blotting were done to confirm the production of truncated protein. Computational three dimensional structure generation through homology modeling approach was done to compare protein structure between patients and controls. Results WES reveled a nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene leading to premature termination codon in mRNA of NPR2 gene resulting in a truncated protein with 204 amino acid residues that was confirmed by SDS-PAGE and Western blotting. Sanger sequencing confirmed that mutation in all subjects and mutation followed Mendalian pattern of inheritance. Multiple sequence alignment by ClustalW revealed that mutated domain of NPR2 is conserved region. Proetin structure comparison revealed a significant structural part of NPR2 was missing in truncated protein as compared to control. Conclusion We are reporting that a novel nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene is causing AMDM in a consanguineous Pakistani family.

Effects of land use and climate variability on the main stream of the Songhua River Basin, Northeast China - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Faisal Baig; Ahmad Niaz; Tianxiao Li (Hydrological Sciences Journal, 2020)

Influence of Crapemyrtle aphid, Tinocallis kahawaluokalani (Hemiptera: Aphididae) on population characteristics of three aphidophagous ladybird beetles - Muhammad Asif Aziz; Habiba Sadaf; Ayesha Iftikhar; Faisal Hafeez (International Journal of Tropical Insect Science, 2020)

Linking environment, malaria, and agricultural returns: a labor time use analysis at different stages of production using 3SLS - Sobia Rose; Muhammad Faisal Ali; Khuda Bakhsh; Muhammad Ashfaq; Sarfraz Hassan (Environmental Science and Pollution Research, 2020)

Sedimentology of Shahejie Formation, Bohai Bay Basin: a case study of Es1 member in Nanpu Sag - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Faisal Rehman; Kamran Shehzad; Muhammad Fahad Ullah; Ghulam Mustafa (Carbonates and Evaporites, 2020)

Recent developments and comparison of transformation strategies for organic halides to aldehydes and ketones - Muhammad Faisal; Aamer Saeed; Danish Shahzad; Parsa Dar; Fayaz Ali Larik (Molecular Diversity, 2020)

Characterization of regional hydrological drought using improved precipitation records under multi-auxiliary information - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Marco Andreas Grzegorczyk; Ibrahim M. Almanjahie; Amna Nazeer; Ishfaq Ahmad (Theoretical and Applied Climatology, 2020)

Synthesis of Ligand Functionalized ErbB-3 Targeted Novel DNA Nano-Threads Loaded with the Low Dose of Doxorubicin for Efficient In Vitro Evaluation of the Resistant Anti-Cancer Activity - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Anam Ahsan; Mehreen Jabeen; Muhammad Asim Farooq; Reyaj Mikrani; Muhammad Abbas; Muhammad Naveed; Said Abasse Kassim; Faisal Raza; Afzal Ahmed Dar; Muhammad Tayyab Ansari (Pharmaceutical Research, 2020)

Association of intronic polymorphisms (rs1549339, rs13402242) and mRNA expression variations in PSMD1 gene in arsenic-exposed workers - Saqiba Ahmad; Bushra Arif; Zertashia Akram; Malik Waqar Ahmed; Asad Ullah Khan; Muhammad Zahid Hussain; Faisal Rahman; Mahmood Akhtar Kayani; Ishrat Mahjabeen (Environmental Science and Pollution Research, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

ASTER-based remote sensing investigation of gypsum in the Kohat Plateau, north Pakistan - Asad Khan; Shah Faisal; Muhammad Shafique; Saad Khan; Alam Sher Bacha (Carbonates and Evaporites, 2020)

Application of non-conventional soft computing approaches for estimation of reference evapotranspiration in various climatic regions - Ali Raza; Muhammad Shoaib; Afzaal Khan; Faisal Baig; Muhammad Abrar Faiz; Mudasser Muneer Khan (Theoretical and Applied Climatology, 2020)

Propagation of the Multi-Scalar Aggregative Standardized Precipitation Temperature Index and its Application - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Dost Muhammad Khan; Rizwan Niaz; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry (Water Resources Management, 2020)

Osmoprotection in plants under abiotic stresses: new insights into a classical phenomenon - Faisal Zulfiqar; Nudrat Aisha Akram; Muhammad Ashraf (Planta, 2020)

An ensemble procedure for pattern recognition of regional drought - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Muhammad Yousuf Shad; Elsayed E. Elashkar; Showkat Gani (International Journal of Climatology, 2020)
Drought being a complex natural hazard is challenging to monitor. Although standardized procedures for drought characterization are commonly used, the uncertainty about accurate drought characterization under various procedures always exists. Therefore, for effective drought mitigation policies, it is necessary to compare the performance of new and the existing drought procedures. In this study, we proposed a new procedure— The Drought Intensity Pattern Determinate (DIPD) to examine and compare the spatial‐temporal intensities of various drought episodes based on Standardized Drought Indices (SDI). The DIPD framework provides a new tool— The Drought Concentration Index ( DCI ) to understand the annual intensity of drought classes by alluding the observed frequencies of drought episodes. At the preliminary level of assessment, DIPD is employed at 52 meteorological stations of Pakistan, and compared three commonly used standardized drought indices: Standardized Precipitation Index (SPI), Standardized Evapotranspiration Index (SPEI) and Standardized Precipitation Temperature Index (SPTI). Exploratory analysis shows a mixed picture as all the drought indices behaving similar for some patterns of drought classes, while some classes show significant discrepancies. In addition, we assessed and compared the spatial distributions using spatial Poisson lognormal model by assuming SDI as a non‐Gaussian process for individual total classes of observed DCI. Results show that the proposed method has ability to incorporate the inner variability in patterns of drought classes. In summary, the DIPD provided a new regional based comparative framework, which accounts the all possible episodes of drought classes and effect of inner discrepancies among quantitative values of SDI.

Understanding the mechanisms of trace organic contaminant removal by high retention membrane bioreactors: a critical review - Muhammad B. Asif; Ashley J. Ansari; Shiao-Shing Chen; Long D. Nghiem; William E. Price; Faisal I. Hai (Environmental Science and Pollution Research, 2019)

Study the stratospheric ozone irregularity over Pakistan atmospheric region in perspectives of wavelet analysis - Bulbul Jan; Muhammad Ayub Khan Yousufzai; Faisal Ahmed Khan Afridi; Faisal Nawaz (Arabian Journal of Geosciences, 2019)

A framework to identify homogeneous drought characterization regions - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Alaa Mohamd Shoukry; Showkat Gani; Ishfaq Ahmad (Theoretical and Applied Climatology, 2019)

Rutin inhibits carfilzomib-induced oxidative stress and inflammation via the NOS-mediated NF-κB signaling pathway - Naif O. Al-Harbi; Faisal Imam; Mohammed M. Al-Harbi; Othman A. Al-Shabanah; Moureq Rashed Alotaibi; Homood M. As Sobeai; Muhammad Afzal; Imran Kazmi; Ammar Cherkess Al Rikabi (Inflammopharmacology, 2019)

Correction to: Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Does globalization increase the ecological footprint? Empirical evidence from Malaysia - Zahoor Ahmed; Zhaohua Wang; Faisal Mahmood; Muhammad Hafeez; Nazakat Ali (Environmental Science and Pollution Research, 2019)

The nexus of renewable and nonrenewable energy consumption, trade openness, and CO2 emissions in the framework of EKC: evidence from emerging economies - Muhammad Wasif Zafar; Faisal Mehmood Mirza; Syed Anees Haider Zaidi; Fujun Hou (Environmental Science and Pollution Research, 2019)

Synergistic effects of chromium and copper on photosynthetic inhibition, subcellular distribution, and related gene expression in Brassica napus cultivars - Lan Li; Meijuan Long; Faisal Islam; Muhammad A. Farooq; Jian Wang; Theodore M. Mwamba; Jianyao Shou; Weijun Zhou (Environmental Science and Pollution Research, 2019)

pH/Thermo-Dual Responsive Tunable In Situ Cross-Linkable Depot Injectable Hydrogels Based on Poly(N-Isopropylacrylamide)/Carboxymethyl Chitosan with Potential of Controlled Localized and Systemic Drug Delivery - Samiullah Khan; Naveed Akhtar; Muhammad Usman Minhas; Syed Faisal Badshah (AAPS PharmSciTech, 2019)

Coal mining trends, approaches, and safety hazards: a brief review - Muhammad Fahad Ullah; Abdullah M. Alamri; Khalid Mehmood; Mian Sohail Akram; Faisal Rehman; Saif Ur Rehman; Omar Riaz (Arabian Journal of Geosciences, 2018)

Correction to: Implication of OPRM1 A118G Polymorphism in Opioids Addicts in Pakistan: In vitro and In silico Analysis - Madiha Ahmed; Ihsan ul Haq; Muhammad Faisal; Durdana Waseem; Malik Mumtaz Taqi (Journal of Molecular Neuroscience, 2018)

Preparation and Evaluation of Skin Wound Healing Chitosan-Based Hydrogel Membranes - Sarfaraz Ahmad; Muhammad Usman Minhas; Mahmood Ahmad; Muhammad Sohail; Orva Abdullah; Syed Faisal Badshah (AAPS PharmSciTech, 2018)

Implication of OPRM1 A118G Polymorphism in Opioids Addicts in Pakistan: In vitro and In silico Analysis - Madiha Ahmed; Ihsan ul Haq; Muhammad Faisal; Durdana Waseem; Malik Mumtaz Taqi (Journal of Molecular Neuroscience, 2018)

Correction to: Pre-existing Small Vessel Disease in Patients with Acute Stroke from the Middle East, Southeast Asia, and Philippines - Naveed Akhtar; Abdul Salam; Saadat Kamran; Atlantic D’Souza; Yahia Imam; Pablo Garcia Bermejo; Muhammad Faisal Wadiwala; Ahmed Own; Ahmed ElSotouhy; Surjith Vattoth; Paula Bourke; Zain Bhutta; et al. (Translational Stroke Research, 2018)

Stream flow variability and drought severity in the Songhua River Basin, Northeast China - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Muhammad Uzair; Muhammad Imran Khan; Faisal Baig; Tianxiao Li; Song Cui (Stochastic Environmental Research and Risk Assessment, 2018)

Salinity reduces 2,4-D efficacy in Echinochloa crusgalli by affecting redox balance, nutrient acquisition, and hormonal regulation - Faisal Islam; Yuan Xie; Muhammad A. Farooq; Jian Wang; Chong Yang; Rafaqat A. Gill; Jinwen Zhu; Weijun Zhou (Protoplasma, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

A Novel Multi-Scalar Drought Index for Monitoring Drought: the Standardized Precipitation Temperature Index - Zuliqar Ali; Ijaz Hussain; Muhammad Faisal; Hafiza Mamona Nazir; Mitwali Abd-el Moemen; Tajammal Hussain; Sadaf Shamsuddin (Water Resources Management, 2017)

MPD3: a useful medicinal plants database for drug designing - Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Farooq Anwar; Faisal Gulzar; Muhammad Amjad Ali; Nazamid Saari; Muhammad Tariq Pervez (Natural Product Research, 2017)

Ethnoveterinary health management practices using medicinal plants in South Asia – a review - Shanoo Suroowan; Faisal Javeed; Mushtaq Ahmad; Muhammad Zafar; Mehwish Jamil Noor; Sadaf Kayani; Ali Javed; Mohamad Fawzi Mahomoodally (Veterinary Research Communications, 2017)

Degradation of Pharmaceuticals and Personal Care Products by White-Rot Fungi—a Critical Review - Muhammad B. Asif; Faisal I. Hai; Lakhveer Singh; William E. Price; Long D. Nghiem (Current Pollution Reports, 2017)

Appraisal for site specific plant nutrient management through spatial variability and mapping in hilly areas of northern Pakistan - Munir Ahmad; Dost Muhammad; Maria Mussarat; Abid Ali Khan; Shah Faisal Khan; Muhammad Waqas Javed (Journal of Soils and Sediments, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Persistent outbreaks of the “black disease” sponge Terpios hoshinota in Indonesian coral reefs - Hawis Madduppa; Peter J. Schupp; Muhammad Reza Faisal; Mustami Yuda Sastria; Carsten Thoms (Marine Biodiversity, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Rutin Attenuates Carfilzomib-Induced Cardiotoxicity Through Inhibition of NF-κB, Hypertrophic Gene Expression and Oxidative Stress - Faisal Imam; Naif O. Al-Harbi; Mohammed M. Al-Harbia; Hesham M. Korashy; Mushtaq Ahmad Ansari; Mohamed M. Sayed-Ahmed; Mahmoud N. Nagi; Muzaffar Iqbal; Md. Khalid Anwer; Imran Kazmi; Muhammad Afzal; Saleh Bahashwan (Cardiovascular Toxicology, 2017)

Dynamic linkages among energy consumption, air pollution, greenhouse gas emissions and agricultural production in Pakistan: sustainable agriculture key to policy success - Muhammad Imran Qureshi; Usama Awan; Zeeshan Arshad; Amran Md. Rasli; Khalid Zaman; Faisal Khan (Natural Hazards, 2016)

Perspectives of using fungi as bioresource for bioremediation of pesticides in the environment: a critical review - Zahid Maqbool; Sabir Hussain; Muhammad Imran; Faisal Mahmood; Tanvir Shahzad; Zulfiqar Ahmed; Farrukh Azeem; Saima Muzammil (Environmental Science and Pollution Research, 2016)

Interrelationships between deformation and metamorphic events across the western hinterland zone, NW Pakistan - Asghar Ali; Mustafa Yar; Muhammad Asif Khan; Shah Faisal (Journal of Earth Science, 2016)

In silico transcriptional regulation and functional analysis of dengue shock syndrome associated SNPs in PLCE1 and MICB genes - Malik Mumtaz Taqi; Durdana Waseem; Humaira Ismatullah; Syed Aleem Haider; Muhammad Faisal (Functional & Integrative Genomics, 2016)

Plant-driven removal of heavy metals from soil: uptake, translocation, tolerance mechanism, challenges, and future perspectives - Sveta Thakur; Lakhveer Singh; Zularisam Ab Wahid; Muhammad Faisal Siddiqui; Samson Mekbib Atnaw; Mohd Fadhil Md Din (Environmental Monitoring and Assessment, 2016)

Evaluation of source rocks using one dimensional maturity modeling in Lower Indus Basin, Pakistan - Faisal Qayyum; Muhammad Hanif; Muhammad Mujtaba; Sohail Wahid; Fahad Ali (Arabian Journal of Geosciences, 2016)

Subcellular distribution, modulation of antioxidant and stress-related genes response to arsenic in Brassica napus L. - Muhammad A. Farooq; Rafaqat A. Gill; Basharat Ali; Jian Wang; Faisal Islam; Shafaqat Ali; Weijun Zhou (Ecotoxicology, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

Reverse ion exchange as a major process controlling the groundwater chemistry in an arid environment: a case study from northwestern Saudi Arabia - Faisal K. Zaidi; Yousef Nazzal; Muhammad Kamran Jafri; Muhammad Naeem; Izrar Ahmed (Environmental Monitoring and Assessment, 2015)

Modulations in plant water relations and tissue-specific osmoregulation by foliar-applied ascorbic acid and the induction of salt tolerance in maize plants - Sidra Jamil; Qasim Ali; Muhammad Iqbal; Muhammad Tariq Javed; Wasif Iftikhar; Faisal Shahzad; Rashida Perveen (Brazilian Journal of Botany, 2015)

Human aging in the post-GWAS era: further insights reveal potential regulatory variants - Syed Aleem Haider; Muhammad Faisal (Biogerontology, 2015)

Priming-induced antioxidative responses in two wheat cultivars under saline stress - Faisal Islam; Tahira Yasmeen; Shafaqat Ali; Basharat Ali; Muhammad A. Farooq; Rafaqat A. Gill (Acta Physiologiae Plantarum, 2015)

Seleniferous soils as a source for production of selenium-enriched foods and potential of bacteria to enhance plant selenium uptake - Muhammad Yasin; Ali F. El Mehdawi; Courtney E. Jahn; Aneela Anwar; Marie F. S. Turner; Muhammad Faisal; Elizabeth A. H. Pilon-Smits (Plant and Soil, 2015)

Effect of diet on preweaning performance of Sahiwal calves - Shaukat Ali Bhatti; Muhammad Faisal Ahmed; Peter Charles Wynn; David McGill; Muhammad Sarwar; Muhammd Afzal; Ehsan Ullah; Musarrat Abbas Khan; Muhammad Sajjad Khan; Russell Bush; Hassan Mahmood Warriach; Ahrar Khan (Tropical Animal Health and Production, 2012)

Identification of the deleterious 2080insA BRCA1 mutation in a male renal cell carcinoma patient from a family with multiple cancer diagnoses from Pakistan - Muhammad U. Rashid; Sidra Gull; Saima Faisal; Saba Khaliq; Kashif Asghar; Neelam Siddiqui; Asim Amin; Ute Hamann (Familial Cancer, 2011)

Comparative assessment of selenite (SeIV) detoxification to elemental selenium (Se0) by Bacillus sp. - Madiha Ikram; Muhammad Faisal (Biotechnology Letters, 2010)

Some new prospects in the understanding of the molecular basis of the pathogenesis of stroke - Sheikh Arshad Saeed; Kaneez Fatima Shad; Taimur Saleem; Faisal Javed; Muhammad Umair Khan (Experimental Brain Research, 2007)

Bacterial Cr(VI) Reduction Concurrently Improves Sunflower (Helianthus Annuus L.) Growth - Muhammad Faisal; Shahida Hasnain (Biotechnology Letters, 2005)

Chromate resistantBacillus cereus augments sunflower growth by reducing toxicity of Cr (VI) - Muhammad Faisal; Shahida Hasnain (Journal of Plant Biology, 2005)

Comparative study of Cr(VI) uptake and reduction in industrial effluent by Ochrobactrum intermedium and Brevibacterium sp. - Muhammad Faisal; Shahida Hasnain (Biotechnology Letters, 2004)

Salinity tolerance and growth response of juvenile Oreochromis mossambicus at different salinity levels - Khalid Jamil; Muhammad Shoaib; Faisal Ameer; Hong Lin (Journal of Ocean University of China, 2004)